Physicochemical Changes, Bioactive Compound Dynamics, and Proteomic Remodeling During Ligustrum sp. Fruit Development - Gilson Gustavo Lucinda Machado; Elda Eller; Ana Beatriz Silva Araújo; Camila Giovana Carvalho Souza; Cháid Acácio António Mussalafo; Carlos Alexandre Rocha da Costa; Sidney Vasconcelos do Nascimento; Sayure Mariana Raad Nahon; Alice de Paula de Sousa Cavalcante; Isa Rebecca Chagas da Costa; Rafael Borges da Silva Valadares; Elisângela Elena Nunes Carvalho; et al. (Plant Molecular Biology Reporter, 2026)

Sensory and volatile profile modulation by plant-derived extracts in fresh meat products: bridging the gap between oxidative stability and consumer acceptance - Nathália Letícia Hernandez Brito; Jhony Silva Ramos; Thais Aparecida Santos; Karina Pinheiro Martins; Gustavo Barreto Costa; Ornella Monique Pereira Ferri; Ana Caroline Silvestre Barbosa Alessi; Ana Elisa Melo da Silva; Francisco Vieira Sales Júnior; Luma Borges de Souza; Guilherme Airam Henz Ferreira Dias; Jayme Rodrigues Dias Júnior; et al. (Trends in Food Science & Technology, 2026)

Three-dimensional laboratory experiments of sediment transfer across a canyon-mouth transition: From landslides to turbidity currents - Richard Eduard Ducker; Alessandro Cantelli; Rafael Manica; George Pantopoulos; Ana Luiza de Oliveira Borges; Carlos Pirmez (Sedimentary Geology, 2026)

Biological control mitigates oxidative stress induced by Tetranychus urticae (Koch) (Acari: Tetranychidae) in cucumber plants - Gizele Martins Pinheiro; Naiara Antonia Nunes Vinhas; Wesley Borges Wurlitzer; Ana Caroline Zanella; Lucélia Hoehne; Maria Goreti De Almeida Oliveira; Julia Renata Schneider; Noeli Juarez Ferla (Acta Physiologiae Plantarum, 2026)
Intensive cucumber cultivation favors the occurrence of pests, particularly Tetranychus urticae (Koch) (Acari: Tetranychidae), which causes damage to leaf tissues, impairing photosynthesis and cellular integrity. Management of this pest is commonly based on chemical control; however, this strategy may intensify oxidative stress in plants. In this context, biological control emerges as a sustainable alternative. This study aimed to evaluate the effects of chemical and biological control on oxidative stress in cucumber plants infested by T. urticae , assessing the action of the pesticide abamectin (Vertimec ® ) and the predator Neoseiulus californicus (McGregor) (Acari: Phytoseiidae) on the modulation of oxidative responses and the maintenance of redox homeostasis. The experiment was conducted under controlled conditions with five experimental groups: untreated control plants, plants infested with T. urticae , infested plants subjected to biological control with N. californicus , infested plants treated with abamectin, and non-infested plants treated with abamectin. Photosynthetic pigments, oxidative stress indicators, and antioxidant enzyme activities were evaluated. Data were subjected to analysis of variance (ANOVA) followed by Tukey’s test ( p ≤ 0.05). Biological control effectively suppressed mite populations while mitigating oxidative damage, whereas chemical control intensified oxidative response, with higher accumulation of reactive oxygen species and increased antioxidant enzyme activity, evidencing an additional metabolic cost to the plants. In contrast, biological control mitigated oxidative damage, maintaining lipid peroxidation levels and enzymatic activity similar to those observed in the control treatment. The use of N. californicus proved to be an efficient and environmentally sustainable strategy for managing T. urticae in cucumber cultivation.

Prevalence and spatial distribution of Brucella spp. seropositive equids from the state of Mato Grosso, Brazil - Nilton Ferreira Borges; Marcelo Luís Barros; Isana Souza Silva; Janice Elena Ioris Barddal; Ana Flávia Borges de Freitas; Melissa Harumi Sumiyoshi; Livia Saab Muraro; Sofia de Souza Pereira Gomes; Anderson Castro Soares de Oliveira; Márcio Garcia Ribeiro; Daniel Moura de Aguiar (Journal of Equine Veterinary Science, 2026)

Aging impact on canine extracellular vesicles production, size, and miRNA content - Clara Luna Marina; Alexandra Mazer Greuel; Lucas de O. Las-Casas; Evilly Lopes-Gomes; Sabrina Simplício de Araújo Romero Ferrari; Marcio Lourenço Rodrigues; Flavia C. G. dos Reis; Anamélia Lorenzetti Bocca; Simoneide Souza Titze-de-Almeida; Fernando Francisco Borges Resende; Fabiano José Ferreira de Sant’Ana; Ricardo Titze-de-Almeida (Veterinary Research Communications, 2026)
Increasing life expectancy has been accompanied by a higher prevalence of age-associated conditions, underscoring the need to better understand biological mechanisms of aging and to identify accessible biomarkers. Extracellular vesicles (EVs) are lipid-bilayer vesicles that mediate intercellular communication by transporting proteins, lipids, and regulatory RNAs, including microRNAs (miRNAs). Here, we investigated whether the abundance, morphology, and molecular cargo of plasma-derived EVs differ between young and senior dogs. Blood samples were obtained from 24 clinically healthy dogs in Gama (Federal District, Brazil), and plasma EVs were isolated by sequential centrifugation, filtration through a 0.22 μm filter, and ultracentrifugation. EVs concentration and size distribution were assessed by nanoparticle tracking analysis (NTA), morphology by transmission electron microscopy (TEM), and cargo by quantification of total protein and sterols using commercial assays. In addition, we quantified miR-19b, miR-29c, miR-7, miR-155, and miR-21 by Real Time Quantitative Polymerase Chain Reaction (RT-qPCR). Senior dogs exhibited a lower plasma EV yield and greater size heterogeneity, with a higher proportion of larger EVs. Total protein and sterol content per starting plasma volume were reduced in the senior group; however, sterol normalized per EV was increased, consistent with compositional remodeling of circulating vesicles with age. Finally, EV-associated miRNA levels were reduced in senior dogs, particularly miR-19b and miR-29c. Collectively, these findings indicate that canine aging is associated with marked changes in plasma EV abundance, morphology, and cargo, indicating that EVs could represent a promising tool for investigating age-related disorders in dogs.

Venom characterization and structural insights into phospholipase D isoforms from the spider Loxosceles aff. variegata - Ana Luiza Silva-Araújo; Rafaela Silva-Magalhães; Pamella Peres-Damásio; Elaine Henriques Teixeira Pereira; Ramon de Oliveira Souza; Luana Silveira da Rocha Nowicki Varela; Luiz Marcelo Ribeiro Tomé; Felipe Campos de Melo Iani; Adriano Lima Silveira; Márcia Helena Borges; Raíssa Medina-Santos; Carlos Chavez-Olórtegui; et al. (Toxicon, 2026)

Cytogenotoxic effects of Artocarpus heterophyllus Lam. leaf extracts: implications for the safe use of medicinal plants - Ellen Borges da Rocha; Renata Gomes Gonçalves; Brenda Christie Castro de Oliveira; Alexia Barreto da Silveira; Ana Beatriz Franco de Jesus; Luiz Carnevale Eberhardt; Débora Moura Peixoto; Brena Guerra Paixão; Matheus de Lima Rodrigues; Alexandre Felipe de Araújo Desidério; Dayana Palmeira da Silva Rosa; Helena Regina Pinto Lima; et al. (South African Journal of Botany, 2026)

Nature's blueprint: Exopolysaccharides linking microbiome dynamics to advanced bone tissue engineering - Ceera Manikandan; Anupama Devi V.K.; Geetha Manivasagam; Ana Pereira; João F. Mano; João Borges; Amit Kumar Jaiswal; Anjaneyulu Udduttula (Carbohydrate Polymers, 2026)

Meteorology, turbulence and indoor–outdoor air quality relationships in two public buildings in Madrid - J.M. Cordero; A. Narros; R. Borge; Andrés Núñez; Ana M. García; E. Díaz-Ramiro; E. Alonso-Blanco; J. Fernández; F.J. Gómez-Moreno; B. Artíñaño; C. Román-Cascón; M. Sastre; et al. (Atmospheric Pollution Research, 2026)

Comprehensive Genomic Characterization and Probiotic Properties Evaluation of Limosilactobacillus fermentum JAC 231 Isolated from Vaginal Microbiota - Carmem Duarte Lima Campos; Amanda Graziella Goncalves Mendes; José Lima Pereira-Filho; Viviane da Silva Sousa Almeida; Ana Beatriz Santos Sousa; Israel Viegas Moreira; João Lucas do Carmo Lima; Aleania Polassa Almeida Pereira; Allysson Kayron Carvalho Silva; Laís Araújo Souza Wolff; Kátia Regina Assunção Borges; Cristianne Roberta Rhoden; et al. (Probiotics and Antimicrobial Proteins, 2026)

Celtis guatemalensis (Cannabaceae: Celtis subg. Celtis), a new tree species from the highlands of Guatemala, with an updated key for Celtis of Mexico and Central America - Knut Eisermann; Henrique Borges Zamengo; Débora Cintia Chamorro; Claudia Avendaño-Mendoza; Rodrigo Faleiro de Lima; Ana Barrios; Luis Javier Aju; Sofía Cabañas (Kew Bulletin, 2026)

Investigation of Genetic Polymorphisms in Inducible Nitric Oxide Synthase and Suppressor of Cytokine Signaling Genes and Pain After Root Canal Treatment - Wayne Martins Nascimento; Erlange Andrade Borges da Silva; Sandra Regina Santos Meyfarth; Ludmila da Silva Guimarães; Ana Grasiela Limoeiro; Heitor Ganier Ribeiro; Erika Calvano Küchler; Flares Baratto-Filho; Alice Corrêa Silva-Sousa; Manoel Damião Sousa-Neto; Lívia Azeredo Alves Antunes; Leonardo Santos Antunes (Biochemical Genetics, 2026)

Thermal treatment of oil-based drill cuttings: A critical review - Simone Kubeneck; Matheus Cavali; Aline Alves Freitas; Diane Osterberg Laroque; Luiza Loss; Gabrielle Machado Ferreira; Ana Calvo; Sebastião Roberto Soares; Armando Borges de Castilhos Junior (Process Safety and Environmental Protection, 2026)

Lupeol as a modulator of bacterial resistance mediated by the MepA efflux pump in Staphylococcus aureus - Nara Juliana Santos Araújo; Camila Aparecida Pereira Silva; Cicera Datiane Morais Oliveira-Tintino; Gabriel Gonçalves Alencar; Maria do Socorro Costa; Ana Raquel Pereira da Silva; Juliete Bezerra Soares; Janaína Esmeraldo Rocha; Saulo Relison Tintino; Vanessa Lima-Bezerra; Henrique Douglas Melo Coutinho; Vanessa Leopoldino Coelho Rodrigues; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Bacterial resistance constitutes one of the main threats to global public health, driving the search for therapeutic strategies capable of restoring the effectiveness of antimicrobials. Among the mechanisms involved, efflux pumps stand out, reducing the intracellular concentration of drugs and contributing to multidrug resistance. In this context, inhibitors of these pumps emerge as a promising approach, as they increase the intracellular concentration of antibiotics. Natural compounds, such as the triterpene lupeol, have been investigated as potential modulators of bacterial resistance due to their relevant biological activities. This study evaluated, from a mechanistic perspective, the ability of lupeol to inhibit the MepA efflux pump in the K2068 strain of Staphylococcus aureus . The minimum inhibitory concentration (MIC) was determined, efflux inhibition assays were performed, membrane permeability analysis was conducted using Sytox Green, ethidium bromide fluorescence was evaluated, RT-qPCR was performed, and molecular docking was performed. The results demonstrated that lupeol exhibits isolated antibacterial activity considered without clinical relevance (MIC ≥ 1024 µg/mL); however, it reduced the MIC of ciprofloxacin and ethidium bromide, indicating inhibition of the MepA pump. No alteration in membrane permeability and an increase in ethidium bromide fluorescence were observed with increasing lupeol concentration. RT-qPCR showed inhibition of mepA gene expression. In molecular docking, the compound presented a binding energy of − 9.01 kcal/mol, with van der Waals, hydrophobic, and hydrogen bonding interactions. It is concluded that lupeol shows potential as an efflux pump inhibitor, acting on the functional inhibition of the pump and the negative regulation of mepA gene expression, thus configuring itself as an adjuvant strategy in combating bacterial resistance.

Combined 2D and 3D cell culture models as a strategy to reduce the use of animals in antitumoral compound screening - Ana Paula Gregório Alves Fontão; Gustavo Werneck de Souza e Silva; Wanise Borges Gouveia Barroso; Gouveia Barroso; André Luiz Franco Sampaio (In vitro models, 2026)

Evaluation of PLA/HA and PLA/HA/G printed scaffolds: influence of graphene and hydroxyapatite on physicochemical and biological properties - Arthur João Reis Lima Rodovalho; Willams Teles Barbosa; Jaqueline Leite Vieira; Caio Athayde de Oliva; Ana Paula Bispo Gonçalves; Izamir Resende Junior Borges Miguel; Josiane Dantas Viana Barbosa (In vitro models, 2026)

Platelet-rich plasma as a xeno-free alternative to fetal bovine serum for in vitro expansion of adipose-derived mesenchymal stromal cells and isolation of extracellular vesicles - Ana Carolina Borges Campos; Anne Moraes de Monção; Natália Ferreira Haddad; Almir Jordão da Silva-Junior; Camila Hubner Costabile Wendt; Ana Célia Sá de Carvalho; Tathiana Proença Pampolha; Leandra Santos Baptista; Ana Luiza Frango de Sant’Anna; Denise de Abreu Pereira; José Marques de Brito Neto; Rosalia Mendez-Otero; et al. (In vitro models, 2026)

Microplastic Interaction in the Parasite Infection of Commercial Marine Puffer Fishes (Tetraodontiformes: Tetraodontidae) of the Campeche Coast, Mexico - Ana Luisa May-Tec; Juan Pablo Ek-Huchim; Edgar Fernando Mendoza-Franco; Jaime Navarro-Flores; Jaime Rendón-Von Osten; Merle M. Borges-Ramírez (Acta Parasitologica, 2026)

Phytochemical contribution of Baccharis cinerea (Asteraceae) to the botanical origin of the greenish-brown propolis from northeastern Brazil - Jônatas Oliveira Costa; Arthur Luy Tavares Ferreira Borges; João Victor Lessa de Oliveira; Gustavo Heiden; Ticiano Gomes do Nascimento; Ana Paula do Nascimento Prata Lins (Vegetos, 2026)

Assessing social–ecological feedbacks in small-scale fisheries - Leandro Castello; Adriana Guimarães Abreu; George Christopher Brooks; João Vitor Campos-Silva; Priscila dos Reis Cunha; Ayan Santos Fleischmann; Caetano Lucas Borges Franco; Ana Claudia Gonçalves; Emma Ann Hultin; Holly Kathleen Kindsvater; Eduardo Guimarães Martins; Cristina Isis Buck Silva; et al. (Ambio, 2026)
Assessment frameworks do not capture the complexity of the social–ecological dynamics of small-scale fisheries (SSF), which support millions of livelihoods yet face persistent sustainability challenges. Reciprocal feedbacks between fish populations and fishers that are central to sustainability remain insufficiently integrated into assessment approaches because conventional fisheries management emphasizes population dynamics, whereas social–ecological systems research focuses on social drivers and faces operational challenges. We propose an integrative diagnostic approach that explicitly links fish population dynamics with theories of fisher behavior and governance. We illustrate its application using co-managed arapaima fisheries in the Amazon Basin, where sustainability emerges from multi-scalar social and ecological interactions. By capturing these feedbacks, the approach bridges ecological and social dimensions to identify key drivers of sustainability. It provides a replicable, interdisciplinary framework for diagnosing SSF sustainability and identifying leverage points to support adaptive governance across diverse contexts.

Fingerprinting and modelling of the Toconao pellet spill in the Iberian Atlantic - Álvaro Cubas; Daura Vega-Moreno; Miriam N. Déniz-Martín; Ana Molina-Rodríguez; Cristina León-Santiago; Javier Hernández-Borges; Francisco Machín; Eugenio Fraile-Nuez (Marine Pollution Bulletin, 2026)

Microzooplankton in the Equatorial Southwestern Atlantic: establishing a baseline for a changing ocean - Ana Cecília Pinho Costa; José Pedro Vieira Arruda Júnior; Letícia Borges Leite; Tatiane Martins Garcia; Sigrid Neumann-Leitão; Marcelo Oliveira Soares (Regional Studies in Marine Science, 2026)

Antipsychotic aripiprazole affects the sexual behavior and biochemical parameters of female Wistar rats - Aline Gabrielle Gomes da Silva; Artemia Kelly Holanda Pereira; Ana Beatriz Silva Angelo; Caio César Araújo dos Santos; Renata Gleysiane de Sousa Felix; Maria Joana Nogueira de Moura; Lícia Gabrielle Gomes de Oliveira; Michelly Fernandes de Macedo; Cibele dos Santos Borges (Reproductive Toxicology, 2026)

Alternative strategic control of Rhipicephalus microplus in the Cerrado of Minas Gerais, Brazil, by exploiting abiotic conditions - Vinicius da Silva Rodrigues; Maria Clara Oliveira Sousa; Rodrigo da Costa Maia; Giovanna Cirqueira Ribeiro Borges; Amanda Ferreira Rezende; Ana Carolina Sousa; Gustavo Martins Felix Silva; Adriane Suzin; Matheus Augusto Ferreira Fernandes; Matias Pablo Juan Szabó (Veterinary Parasitology, 2026)

Mixotrophic cultivation of Arthrospira platensis with regional natural substrates: Sustainable biomass and bioproduct production in a circular economy - Warlen Agnelo Dias; Ana Célia Freitas Bernardo; Erisson Paulo Borges Lopes; Antonio Zuorro; Fabiana Regina Xavier Batista; Erika Ohta Watanabe; Juliana de Souza Ferreira (Algal Research, 2026)

The action of selected monoterpenes as biofilm control agents and antibiotic resistance modifiers - Francisca Massano; Ana C. Afonso; Mariana Sousa; Lília S. Teixeira; Anabela Borges; Manuel Simões (Biofouling, 2026)

Detection of Brucella spp. in compost-bedding pack barn and its relationship with infections in dairy cows during the transition period - Marcilene Daniel Damasceno; Maysa Serpa Gonçalves; Maria Eduarda de Souza Teixeira Campos; Amanda Carvalho Rosado Ferreira; Dircéia Aparecida Costa Custódio; Eduarda Moraes Magossi Silva; Vivian Aparecida Malta; Alice Gonçalves dos Reis; Bruno Borges Silva; Ana Clara de Serpa Carvalho; Júlia Lima Paz; Pedro Felipe Rodrigues e Oliveira; et al. (Research in Veterinary Science, 2026)

Biostimulant Potential of Vitamins in Soybean Cultivation - Vitória Carolina Dantas Alves; Sebastião Ferreira de Lima; Eduardo Pradi Vendruscolo; Travis Wilson Witt; Arthur Renan Fernandes Nogueira; Laura Martins Ferreira; João Flávio Floriano Borges Gomides; Evelyn Rodrigues de Lacerda; Cassio de Castro Seron; Ana Paula Leite de Lima (International Journal of Plant Production, 2026)

Evaluation of the effects of hybrids of metronidazole and eugenol analogues as inhibitors of the Staphylococcus aureus NorA efflux pump: an in vitro and in silico analysis - Lucas dos Santos Sa; João Arthur de Oliveira Borges; Francisco Ruan Moreira da Silva Santos; Cicera Laura Roque Paulo; Daniel Sampaio Alves; Ewerton Yago de Sousa Rodrigues; Ray Silva de Almeida; Sheila Alves Gonçalves; Cícera Datiane de Morais Oliveira Tintino; Lucas Lopardi Franco; Ana Laura Marques Trinca; Douglas Henriques Novais; et al. (Folia Microbiologica, 2026)
Staphylococcus aureus is a Gram-positive coccus-type bacterium responsible for colonizing various sites of the host’s body, thus generating several pathologies such as pneumonia, osteomyelitis, endocarditis, and even cases of sepsis. Eugenol, dihydroeugenol, guaiacol, and phenol are phenolic compounds with antimicrobial activities, as is the drug metronidazole; therefore, eight substances were synthesized by coupling metronidazole with the molecules mentioned above, thus originating the compounds AD1–AD8. The present study aimed to evaluate the antibacterial activity and the capacity of the compounds AD1–AD8 to amplify the action of norfloxacin and ethidium bromide against the S . aureus 1199B strain through the inhibition of the NorA efflux pump. Broth microdilution assays were performed to determine the MIC and to analyze the association of the compounds AD1–AD8 with norfloxacin and ethidium bromide, along with the membrane permeability test and molecular docking. The compounds AD1–AD8 obtained positive results as they exhibited a potentiating effect by reducing the MIC of norfloxacin and ethidium bromide against 1199B, thus evidencing interference with the functioning of the NorA efflux pump, which had already been predicted by the data obtained from the molecular docking assay, in addition to having demonstrated significant effects by acting on the S. aureus membrane. The information obtained from this research is in line with what is reported in the literature regarding the effects observed with eugenol, dihydroeugenol, and guaiacol and their derivatives when combined with other antibiotics against S. aureus strains that possess efflux pumps, with competitive inhibition being observed, as well as the possibility that the reduction in MIC may have occurred due to a reduction in gene expression levels. Further assays are needed to evaluate these possibilities. Based on the presented data, it was found that the compounds AD1–AD8 exhibit promising aspects to act as antibiotic adjuvants.

Botanical insecticides for the sustainable management of Leucoptera coffeella in coffee crops: Impacts on immature and adult stages under laboratory conditions - Wesley Borges da Silva Bordinhon; Andriely Borges da Silva; Jonas Mendes Rodrigues Souza; Isabela Andrade Costa; Mônica Cristina Alves Soler; Ana Victoria Morais Guidotti Luz; Alessandra Marieli Vacari (Crop Protection, 2026)

In vitro and in silico evaluation of nematicidal lectin compounds from Artocarpus heterophyllus seeds targeting gastrointestinal helminths - Renata Cristina Borges da Silva Macedo; Mirna Samara Dié Alves; Francisco Chagas Barbalho Neto; Pablo Leandro Filgueira Feitosa; Mário Luan Silva de Medeiros; Edgley Alves de Oliveira Paula; Michele Dalvina Correia da Silva; Ana Carla Diógenes Suassuna Bezerra (Veterinary Parasitology, 2026)

Association of iodine nutritional status with thyroid nodules and papillary thyroid carcinoma in women from an iodine-sufficient region in Brazil: A cross-sectional center study - Ivia Fonseca; Aline Larcher de Almeida; Patrícia Borges dos Santos; Natalia Treistman; Tales Aprigio; Mario Vaisman; Ana Paula Aguiar Vidal; Patrícia de Fátima dos Santos Teixeira; Nathalie Silva de Morais (Journal of Trace Elements in Medicine and Biology, 2026)

Red light–mediated enhancement of the antifungal activity of Physalis angulata against Candida species - Bianca Borges de Alencar; Maria Laura Faleiros Ribeiro de Melo; Wanderson Zuza Cosme; Matheus Henrique Francisco Dias; Camila Cristina Baccetti Medeiros; Rodrigo Sorrechia; Rosemeire Cristina Linhari Rodrigues Pietro; Fabiano Guimarães Silva; Marcio Luís Andrade e Silva; Wilson Roberto Cunha; Patrícia Mendonça Pauletti; Regina Helena Pires; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Effect of culture medium composition, incubation time, and temperature on the biofilm-forming ability of Aspergillus westerdijkiae - Angélica Olivier Bernardi; Juliana Copetti Fracari; Pâmela Oliveira Soares; Luciane Vieira Borges Gós; Paula Fernanda Pinto da Costa; Ana Flávia Furian; Marina Venturini Copetti (Food Research International, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Impact of genetic selection for postweaning weight on the reproductive development of young Nellore bulls - Marcelo Sant’Ana Borges; Letícia Padovani da Silva; Marina de Oliveira Silva; Mariana Karla Francolino da Silva; Victor Guidi Zardo; Laura Fernanda Sechirolli Silva; Ricardo Dutra Do Bem; André Maciel Crespilho; Maria Eugênia Zerlotti Mercadante; Fabio Morato Monteiro (Animal Reproduction Science, 2026)

Vertical distribution and composition of microplastics and marine litter in the open ocean surrounding the Canary Islands (0–1200 m depth) - Ana Molina Rodríguez; Miriam Noemí Déniz Martín; Elsa María Rodríguez Pérez; Joséphine Amey; Javier Hernández Borges; Eugenio Fraile Nuez; Francisco Machín; Daura Vega Moreno (Marine Pollution Bulletin, 2026)

Beneficial effect of AntiOxBEN2, a mitochondria-directed antioxidant, on maturation of bovine oocytes: Analysis of bioenergetics pathways and embryo production - Filipa Ferreira; Camila Teixeira; José Teixeira; Joana Jorge; Fernando Cagide; Fernanda Borges; José A.M. Prates; Fernando Lidon; Ana Cristina Gonçalves; Paulo J. Oliveira; Rosa M.L.N. Pereira (Theriogenology, 2026)

Microplastics in Brazilian rivers: An overview and a study of floating particle accumulation on the coast of Santa Catarina state - Igor Marcon Belli; Eliziane Silva Vieira; Ana Ramos Oliveira; Lígia Pinto; Luis H.P. Garbossa; Rémy Bayard; Davide Franco; David Valença Dantas; Armando Borges de Castilhos Junior (Science of The Total Environment, 2026)

Exploring the Antimicrobial Potential of a Peptide Against Mixed Biofilm of Staphylococcus aureus and Candida albicans - Graziela Custódia Sandim; Janaina de Cássia Orlandi Sardi; Amanda Carolina Borges da Silva; Leticia Souza Lima; Eduardo Benedetti Parisotto; Edson Crusca Junior; Ana Cristina Jacobowski; Maria Ligia Rodrigues Macedo (Probiotics and Antimicrobial Proteins, 2026)

Modulation of cardiac contractility and redox balance via cannabinoid type II receptor activation in healthy rats - Suzana Luisa Alves Fernandes; Yan Costa Gonçalves; Francisco Tadeu Rantin; Ana Lúcia Kalinin; José Wilson Magalhães Bassani; Rosana Almada Bassani; Guilherme Borges Pereira; Diana Amaral Monteiro (Pflügers Archiv - European Journal of Physiology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Toward Ocean Model-Driven Robotic Exploration - Renato Mendes; Ana Duarte; Leonardo Azevedo; Lucrezia Bernacchi; João Borges de Sousa; João Pereira; Bernardo Gabriel; João Bogas; Marina Cunha; Clara Rodrigues; Ajit Subramaniam; Fernando Esteves; et al. (Oceanography, 2026)
This interdisciplinary work demonstrates the viability of coupling ocean models with in situ robotic sampling in a dynamic coastal region as a means to increase model skill and prediction. Model-driven exploration closes the sample-assimilate-​predict-direct loop within a virtuous cycle to refine prediction for a range of applications in a region characterized by harsh conditions, high variability, and diverse physical forcings, including bathymetry and coastal topography. By exploring the feasibility of coupling high-resolution autonomous underwater vehicle (AUV) sampling and data assimilation with a geostatistical model in a continuous loop, we aim to provide a new approach to understanding coastal dynamics and processes, while using modest computational resources. The novelty of this effort is threefold: the demonstration of coupling models with AUV sampling, the importance of targeted sampling, and the impact of loop closure toward model prediction.

Cytotoxic and immunotoxic profile of HgCl2 involves alterations in purinergic signaling through the P2X7/NLRP3/CASP-1/IL-1β pathway: An in vitro study using human blood immune cells - Mairin Schott; Charles Elias Assmann; Bianca Vedoin Copês Rambo; Marcylene Vieira da Silveira; Milagros Fanny Vera Castro; Vitor Bastianello Mostardeiro; Adriel Antônio Schirmann; Robson Lourenço da Silva Santos; Pâmela de Almeida Milioni; Ana Barbosa Viana; Valderi Luiz Dressler; Daniel Lázaro Gallindo Borges; et al. (Toxicology in Vitro, 2025)

Direct and intergenerational effects in reproductive parameters of adult male Wistar rats and their offspring after subchronic exposure to polystyrene nanoplastics - Lethícia Valencise; Ana Flávia Quiarato Lozano; Jorge Willian Franco de Barros; Carina Funck Godoy; Cibele dos Santos Borges; Daniel G. Cyr; Wilma De Grava Kempinas (Reproductive Toxicology, 2025)

The Effect of Lacticaseibacillus rhamnosus, Lacticaseibacillus paracasei, and Bifidobacterium animalis ssp. lactis on the Prevention of Asthma in an Animal Model - Líris Marini Dias Coelho; Vanessa Maciel Braulio da Fonseca; Ivana Golçalves Labadessa; Sergio Luiz Salvador; Marina Del Arco Mastrange; Ana Flávia Gembre; Núbia Sabrina Martins; Vânia Luiza Deperon Bonato; Élcio Oliveira Vianna; Marcos Carvalho Borges (Probiotics and Antimicrobial Proteins, 2025)

Achieving greater accuracy in transcranial magnetic stimulation corticospinal evaluation and motor mapping by improving motor evoked potential recording: an emerging issue - Marco Antonio Cavalcanti Garcia; Ana Carolina Borges Valente; Victor Hugo Moraes; Daniela Morales; Lucas dos Santos Betioli (Physical and Engineering Sciences in Medicine, 2025)

Citric acid as a safe alternative to oxalic acid in the Gomori reticulin technique: a comparative study - Ana Bento; Ana Nascimento; Sofia Nobre; Teresa Ferreira; Amadeu Borges-Ferro; Ana Marques-Ramos (Histochemistry and Cell Biology, 2025)
The use of oxalic acid is common in metallic impregnation techniques, where it serves as a reducing and bleaching agent for potassium permanganate. Given that oxalic acid is harmful to health, its replacement with another reagent is advantageous for healthcare professionals handling it in laboratory settings. Considering that citric acid can also reduce potassium permanganate, the aim of this study was to determine whether oxalic acid in the Gomori reticulin technique could be replaced by citric acid, a compound substantially less hazardous to health. To this end, 1%, 5%, and 10% citric acid solutions were tested on porcine liver and kidney samples, and the intensity of reticulin fiber staining, contrast, and overall morphological preservation were assessed in comparison with 1% oxalic acid. The results showed no statistically significant differences between the positive control (oxalic acid) and the citric acid protocols, with the 5% citric acid concentration proving most favorable in terms of required incubation time and the evaluated morphological parameters. It was therefore concluded that citric acid can be used as a bleaching agent for potassium permanganate in the Gomori technique, effectively replacing oxalic acid.

Bed roughness in gravel-bed rivers: Channel-scale responses to flow and sediment dynamics - Danrlei de Menezes; Ana Luiza Oliveira Borges (Advances in Water Resources, 2025)

Exploring the Sleep Quality and Associated Factors Among Truck Drivers in Brazilian Highways: A Cross-Sectional Study - Paulo M. A. Lima; Josiane S. Souza; Ana C. S. Feliciano; Heloísa S. Guerra; Poliana P. Ghazale; Fábio V. A. Borges; Alessandro R. Giovani; Renato C. D. Silva (Sleep and Vigilance, 2025)

Reproductive Behavior and Stridulatory Communication in Euscepes postfasciatus (Coleoptera: Curculionidae) - Alice Pereira de Freitas; Maria Carolina Blassioli-Moraes; Miguel Borges; Ana Cristina Meneses Mendes Gomes; Miguel Michereff Filho; Raúl Alberto Laumann (Neotropical Entomology, 2025)

Cordiaquinone B induces cytotoxicity and oxidative stress-mediated apoptosis in human colorectal cancer cells in vitro and in vivo - Stéphanie Aguiar de Negreiros Matos Silva; Fabrício dos Santos Machado; Luciano de Souza Santos; Maria Victoria Lima de Castro; Mateus Lima Nogueira; Milena Botelho Pereira Soares; Simone Alves Serafim Rocha; Renata Mendonça Araújo; Rosane Borges Dias; Daniel Pereira Bezerra; Ana Jérsia Araújo; José Delano Barreto Marinho Filho (Chemico-Biological Interactions, 2025)

Seroconversion after autogenous vaccination against mastitis in crossbred dairy cows - Ana Cláudia Fagundes Faria; Carla Cristian Campos; Paulo César Franco Dutra; Felipe Zanforlin Freitas; Roberta Tomaz Botta França; Isabela Pacheco Borges; José William Maluf de Paula; Ricarda Maria dos Santos (Tropical Animal Health and Production, 2025)

Geostatistical uncertainty maps for real-world efficient AUV data collection - Ana F. Duarte; Lucrezia Bernacchi; Renato Mendes; João Borges de Sousa; Leonardo Azevedo (Frontiers in Marine Science, 2025)
Autonomous Underwater Vehicle (AUV) trajectory planning for oceanographic surveys is challenging and requires comprehensive and efficient data collection for enhanced mission success. By strategically navigating and targeting high-value data points, the AUV can operate longer and gather more essential information for numerical ocean model calibration. Here, we propose a geostatistical modelling workflow with two complementary objectives. First, to jointly predict ocean temperature and spatial uncertainty maps, representing regions with limited knowledge about the ocean properties of interest, from where optimized navigation paths can be devised and updated. Second, to efficiently assimilate the collected data and update an ocean model with the new data. An autonomous oceanographic survey performed off W. Portugal illustrates the proposed modelling workflow. We use the CMEMS product of Atlantic-Iberian-Biscay-Irish-Ocean Physics Analysis and Forecast as a priori and conditioning data of the spatial predictions. During the survey, the data acquired by the AUV are assimilated and used in new geostatistical predictions for the day after the data acquisition. The results show that the proposed methodology efficiently predicts daily ocean temperature and its spatial uncertainty, allowing data assimilation from different sources (i.e., numerical models of ocean dynamics and AUV sampling). This approach enables the assimilation of AUV measurements and the model prediction to have higher value and greater reliability.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Unravelling the potential mechanisms of nano- and microplastic toxicity to the male reproductive system: A systematic review - Paloma da Cunha de Medeiros; Aline Gabrielle Gomes da Silva; Ana Beatriz Silva Angelo; Maria Joana Nogueira de Moura; Unnikrishnan Kannan; Mary Gregory; Julie Dufresne; Cibele dos Santos Borges; Daniel G. Cyr (Reproductive Toxicology, 2025)

Exploring the therapeutic synergy: comprehensive assays unveil the potential of sericin and Chelidonium majus L. in developing a possible wound dressing - Ana Borges; Sandrina A. Heleno; Sónia P. Miguel; Maximiano P. Ribeiro; Paula Coutinho; André F. Moreira; María Luisa Martín Calvo; Josiana A. Vaz; Lillian Barros; Ricardo C. Calhelha (Phytochemistry Letters, 2025)

Enhancing wound healing: sericin and Chelidonium majus L. as potential dressings - Ana Borges; María Luisa Martín Calvo; Sandrina A. Heleno; Sónia P. Miguel; Maximiano P. Ribeiro; Paula Coutinho; André F. Moreira; Josiana A. Vaz; Lillian Barros; Ricardo C. Calhelha (Phytochemistry Letters, 2025)

Season and temperature-humidity index affect sperm quality and in vivo fertility of beef bulls - Larysse A. Alves; Reinaldo F. Cooke; Marcelo Sant’Ana Borges; Fabiana F. Souza; John P. Kastelic; André M. Crespilho (Journal of Thermal Biology, 2025)

Selenite protects human peripheral blood mononuclear cells (PBMCs) from CdCl2 cytotoxicity - Anieli Golin; Ana Barbosa Viana; Valderi Luiz Dressler; Daniel Lázaro Gallindo Borges; Michael Aschner; Alexey Tinkov; João Batista Teixeira da Rocha (Journal of Trace Elements in Medicine and Biology, 2025)

Chemometric discrimination of airborne fibres: microplastics, regenerated cellulose and natural fibres - Carlos Edo; Marica Erminia Schiano; Sergio J. Álvarez-Méndez; Javier Hernández-Borges; Daura Vega-Moreno; Ana Molina-Rodríguez; May Gómez; Alicia Herrera; Miguel González-Pleiter; Francisca Fernández-Piñas; Roberto Rosal (Environmental Research, 2025)

Feline botulism: two decades and two reports - Ísis Assis Braga; Nicoly Ferreira de Urzedo; Guilherme Oliveira Maia; Ana Paula Carvalho Gomes; Raiany Borges Duarte; Bruna Samara Alves-Ribeiro; Andressa da Silva Martins; Tamires Ataides Silva; Luiz Henrique Barbosa Pires; Stéfanne Rodrigues Rezende; Nathalia de Assis Pereira; Raquel Loren dos Reis Paludo; et al. (Veterinary Research Communications, 2025)

Threats and conservation status of the endemic terrestrial arthropods of the Azores - Guilherme Oyarzabal; Gabor Pozsgai; Noelline Tsafack; Pedro Cardoso; François Rigal; Mário Boieiro; Ana M.C. Santos; Isabel R. Amorim; Jagoba Malumbres-Olarte; Ricardo Costa; Sébastien Lhoumeau; Rosalina Gabriel; et al. (Biological Conservation, 2025)

Revisiting the emergence of the Chikungunya virus in Alagoas, Northeast of Brazil - Mykaella Andrade de Araújo; Ana Carla Eugênio Lima; Jean Phellipe Marques do Nascimento; Ana Paula Andreolla; Thiago Pina Goes de Araújo; Michel Alves do Nascimento; Ana Rachel Vasconcelos de Lima; Magliones Carneiro de Lima; Hazerral de Oliveira Santos; Anderson Brandão Leite; Juliano Bordignon; Claudia Nunes Duarte dos Santos; et al. (Brazilian Journal of Microbiology, 2025)

Effect of injection conditions on the efficiency of intrafollicular immature oocyte transfer (IFIOT) - Ana Caroline Chaves Vall Nicolás; Otávio Augusto Costa de Faria; Marcelo Sant Ana Borges; Nayara Ribeiro Kussano; Ivo Pivato; Carlos Frederico Martins; José Felipe Warmling Sprícigo; Margot Alves Nunes Dode (Theriogenology, 2025)

A validated ultra-performance liquid chromatography with tandem mass spectrometry method for the quantification of Brazilian green propolis main compounds - Mário Ferreira Conceição Santos; Giulia Stavrakas Mirada; Joice Olinda do Couto; Gilvana de Oliveira Costa; Ana Carla Rangel Rosa; Carly Henrique Gambeta Borges; Eduardo José Crevelin; Luciana Silva de Araújo; Jairo K. Bastos; Rodrigo C. S. Veneziani; Sérgio R. Ambrósio (Natural Product Research, 2025)

Exposure to emerging water contaminants and human health risk: Cytotoxic and genotoxic effects of caffeine and diethyltoluamide (DEET) on eukaryotic cells - Juliana Picinini-Zambelli; Ana Letícia Hilário Garcia; Malu Siqueira Borges; Enaile Tuliczewski Serpa; Fernanda Rabaioli da Silva; Rafael Rodrigues Dihl; Juliana da Silva (Chemosphere, 2025)

Soil quality changes in cashew orchard production in Brazilian semiarid areas: a comprehensive field survey across locations, seasons, tree types, and management practices - Arlene Santisteban Campos; Ederson da Conceição Jesus; Paulo Furtado Mendes Filho; Arthur Prudêncio de Araújo Pereira; Ana Cecília Ribeiro de Castro; Arthur Cesar Mina Albuquerque Coelho; Patricia do Nascimento Bordallo; Wardsson Lustrino Borges; Ana Cristina Portugal Pinto de Carvalho (Applied Soil Ecology, 2025)

First isolation of Leptospira interrogans from follicular fluid of naturally infected cows - Ana Luiza dos Santos Baptista Borges; Luiza Aymée; Isabel Roussouliéres; Filipe Anibal Carvalho-Costa; Maria Isabel Nogueira Di Azevedo; Walter Lilenbaum (Veterinary Microbiology, 2025)

Non-linear homogenization of small mammal communities following habitat loss in a biodiversity hotspot - Ana Cláudia Delciellos; Vitor Nelson Teixeira Borges-Júnior; Rui Cerqueira; Marcus Vinícius Vieira; Jayme Augusto Prevedello (Biological Conservation, 2025)

Acute and chronic post-COVID-19 conditions: A study of genetic integrity and clinical markers - Bruna Alves Alonso Martins; Ana Leticia Hilario Garcia; Malu Siqueira Borges; Daiane Dias Ribeiro Nobles; Alana Witt Hansen; Fernando Rosado Spilki; Lavínia Schuler-Faccini; Pabulo Henrique Rampelotto; Juliana da Silva (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Gluten-free cookies: A comprehensive review of substitutes for wheat flour - Rafael Fernandes Almeida; Lara Aguiar Borges; Daniel Anacleto; Miriam Stephanie Nunes de Souza; Licymara Brianne Magalhães da Silva; Yaneth Machaca Monroy; Eduardo Augusto Caldas Batista; Ana Paula Oliveira Machado (Food and Humanity, 2025)

The role of mitochondrial dysfunction and calcium dysregulation in 2C-I and 25I-NBOMe-induced neurotoxicity - Eva Gil-Martins; Fernando Cagide; Ana Borer; Daniel José Barbosa; Carlos Fernandes; Daniel Chavarria; Fernando Remião; Fernanda Borges; Renata Silva (Chemico-Biological Interactions, 2025)

Effect of liming using Lithothamnium calcareum on atrazine and S-metolachlor leaching and persistence in soil - Gabriella Francisco Pereira Borges de Oliveira; Rita de Cássia Silva; Gabriela de Souza da Silva; Ana Carolina Oliveira Chapeta; Lucas Rêgo Mendonça Marinho; Monique Macedo Alves; Jonathan Almeida Santos Simões; Everaldo Zonta; Camila Ferreira de Pinho (Environmental Science and Pollution Research, 2025)

Effects of sunflower cake in lamb diets on meat quality and its fatty acid profile - Ana Cláudia da Costa; Alessandra Schaphauser Rosseto Fonseca; Matheus Lima Corrêa de Abreu; Nelcino Francisco de Paula; Joanis Tilemahos Zervodakis; Luciana Kimie Savay da Silva; Quezia Pereira Borges da Costa; Dorival Pereira Borges da Costa; Roberto de Oliveira Roça; Deivison Novaes Rodrigues; Fagton de Mattos Negrão; Luciano da Silva Cabral (Tropical Animal Health and Production, 2025)

Influence of animal temperament on body and reproductive development of beef bulls - Mariana Karla Francolino da Silva; Marcilio Nichi; Marcelo Sant’Ana Borges; Richardt Gama Landgraf; Marcelo Francisco Arantes Pereira; André Maciel Crespilho (Animal Reproduction Science, 2025)

Dual modification of starch: Synergistic effects of ozonation and pulsed electric fields on structural, rheological, and functional attributes - Raphael Lucas Jacinto Almeida; Newton Carlos Santos; Ana Carla Oliveira de Brito; Ana Carolina Nóbrega Leite; Jessica Renaly Fernandes Morais; Bárbara Freire de Oliveira; Paloma Benedita da Silva; Ynis Thaciane Felix da Silva; Raimunda Valdenice da Silva Freitas; Karina Soares do Bonfim; Alison Bruno Borges de Sousa; Maria José de Figueiredo; et al. (Food Chemistry, 2025)

Equine endometrial bacteria inhibition by metabolite and extracellular vesicles of Lactobacillus acidophilus and lactiplantibacillus plantarum - Maria Clara Mendes Bernabe; Belchiolina Beatriz Fonseca; Maysa Vitória Cunha Silva; Isabelle Ezequiel Pedrosa; Michelle Borges Silva; Simone Sommerfeld; Amanda Luiza Pereira de Sousa; Bruna Candelori de Leva Resende; Ana Carolina Prado Sousa; Andria dos Santos Freitas; Vasco Ariston Carvalho de Azevedo; Éric Guédon; et al. (Veterinary Research Communications, 2025)

Cardiotoxicity Associated With a Low Doses of 5-FU Promotes Morphoquantitative Changes in the Intrinsic Cardiac Nervous System - Karile Cristina da Costa Salomão; Mariana Conceição da Silva; Lilian Catarim Fabiano; Pedro Luiz Zonta de Freitas; Camila Quaglio Neves; Stephanie Carvalho Borges; Ana Cristina Breithaupt-Faloppa; Carmem Patrícia Barbosa; Nilza Cristina Buttow (Cardiovascular Toxicology, 2025)

Ephestia kuehniella Zeller eggs as a surrogate host to test feeding preference and intraguild interactions between Macrolophus pygmaeus (Rambur) and Trichogramma achaeae Nagaraja and Nagarkatti - António O. Soares; Ana C. Durão; Luisa Oliveira; Patrícia Arruda; Isabel Borges (Crop Protection, 2025)

Effects of environmental temperature and humidity on sperm quality of bulls of different ages - L.A. Alves; R.F. Cooke; Y.E. Hayek-Martins; F.F. Souza; M. Sant’Ana-Borges; L.F. Canela Souza; N.S. Gonçalves; A.M. Crespilho (Animal Reproduction Science, 2025)

Impact of seasons and age on fertility of bulls - Yasmin El Hayek-Martins; Reinaldo Fernandes Cooke; Larysse Aparecida Alves; Fabiana Ferreira Souza; Marcelo Sant’Ana-Borges; Juliana Varchaki Portes; Fabiola Aparecida Afonso; Andre Maciel Crespilho (Animal Reproduction Science, 2025)

Sex-related differences in eating behaviors during COVID-19 pandemic: A systematic review with metanalysis - Simone Gonzaga do Carmo; Maísa Miranda Araújo; Maria Eduarda Coelho Bittencourt Cavalcanti; Ana Claudia Morais Godoy Figueiredo; Kênia Mara Baiocchi de Carvalho; Patrícia Borges Botelho (Appetite, 2024)

Heat shock on bovine embryos from day 2.5–3 selects the most competent for progression to the blastocyst stage - Luciano de Rezende Carvalheira; Ana Carolina Leite Albeny; Eliane Beatriz Magalhães Silva; Álan Maia Borges (Theriogenology, 2024)

Combined effects of high hydrostatic pressure and pulsed electric fields on quinoa starch: Analysis of microstructure, morphology, thermal, and pasting properties - Raphael Lucas Jacinto Almeida; Newton Carlos Santos; Marcelo da Silva Pedro; Iêda Leticia de Souza Ferreira; Raphael da Silva Eduardo; Cecilia Elisa Sousa Muniz; Vitória de Andrade Freire; Ana Carolina Nóbrega Leite; Bárbara Freire de Oliveira; Paloma Benedita da Silva; Ynis Thaciane Felix da Silva; Raimunda Valdenice da Silva Freitas; et al. (Food Chemistry, 2024)

Nanofiber-boosted retrograded starch/pectin microparticles for targeted 5-Aminosalicylic acid delivery in inflammatory bowel disease: In vitro and in vivo non-toxicity evaluation - Andréia Bagliotti Meneguin; Cesar Augusto Roque-Borda; Ana Beatriz Grotto Piperas; Maria Fernanda Ortolani Pollini; Vinicius Martinho Borges Cardoso; Laura Maria Duran Gleriani Primo; Forogh Alemi; Fernando Rogério Pavan; Marlus Chorilli (Carbohydrate Polymers, 2024)

Sulfated polysaccharide extracted from the alga Gracilaria domingensis modified with propionic anhydride negatively modulates acute inflammation and experimental hypernociception - Jayro dos Santos Ferreira; Rafael da Silva Prudêncio; Antonio Kleiton de Sousa; Stefany Guimarães Sousa; Fernando Mesquita de Sousa de Lima; André dos Santos Carvalho; Ana Clara Coelho da Costa; Denise Mayara Melo Silva; Maria da Graça Sales Furtado; Danyela Maria Leal Rocha; Vanderlene Oliveira Rodrigues; Daniel Fernando Pereira Vasconcelos; et al. (Bioactive Carbohydrates and Dietary Fibre, 2024)

Is microscopic agglutination test a reliable method for diagnosing the bovine genital leptospirosis syndrome? - Luiza Aymée; Ana Luiza Dos Santos Baptista Borges; Guilherme Nunes de Souza; Walter Lilenbaum (Veterinary Research Communications, 2024)

Colonisation by multidrug-resistant organisms in health workers in primary care: narrow spectrum oral antimicrobials are a risk factor - Vítor Falcão de Oliveira; Letícia Fernandes de Britto-Costa; Gabrielly Lacerda de Aragão; Nazareno Scaccia; Ana Carolina Mamana; Marina Farrel Côrtes; Maura Salaroli de Oliveira; Bruno de Melo Tavares; Erika Regina Manuli; Fábio Eudes Leal; Gabriela Tonon de Oliveira Xavier; Regina Maura Zetone Grespan; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Correction: Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

Profile of urban sustainability in Bulgaria - Margarida Rodrigues; Mário Franco; Hristina Filipova; Rui Jorge Silva; Velina Kazandzhieva; Radka Nacheva; Velina Koleva; Lyubomir Lyubenov; Cidália Oliveira; Ana Pinto Borges; José Braga; Pavlina Ivanova; et al. (Environment, Development and Sustainability, 2024)
Sustainability is becoming increasingly relevant due to the need to decide on planned management of land use and natural resources as well as sustainable development in the context of cities. This study aims to identify indicators for measuring the sustainable development of districts/countries in Bulgaria. Using the Multivariate Analysis (MVA) method, where we examine multiple variables in several dimensions, the results show that in the environmental pillar, the management of natural resources, including water and soil, was under pressure due to industrial and urban activities. Air quality and waste management were also critical issues in some urban areas. The promotion of sustainable building practices and the adoption of renewable energies could be areas of focus for improving environmental sustainability in Bulgarian cities. This study is innovative becouse it underscores the imperative need for urban sustainability to integrate the foundational pillars of sustainability harmoniously. Central to this integration is the cultivation of economic growth that upholds environmental integrity and fosters social equity and opportunity. More theorectical and managerial contributios are also presented.

Effects of LED lights and cytokinin on the phytotreatment of simulated swine wastewater by Azolla spp.: Pollutant removal and biomass valorization - Eder Carlos Lopes Coimbra; Alisson Carraro Borges; Ana Beatriz Carvalho Bastos; Ann Honor Mounteer; André Pereira Rosa (Water Research, 2024)

Molecular epidemiology of Leptospira spp. serogroup Sejroe associated with chronic bovine leptospirosis - Ana Luiza dos Santos Baptista Borges; Luiza Aymée; Filipe Anibal Carvalho-Costa; Walter Lilenbaum; Maria Isabel Nogueira Di Azevedo (Veterinary Microbiology, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Beyond the surface: microbiological and biochemical attributes as indicators of soil quality in Atlantic Forest ecosystem - Nicácio de Oliveira Freitas; Danielle Karla Alves da Silva; Indra Elena Costa Escobar; Fábio Sérgio Barbosa da Silva; Daniele Magna Azevedo de Assis; Ana Carolina Borges Lins-e-Silva; Maria Jesus Nogueira Rodal; Leonor Costa Maia (CATENA, 2024)

Injectable progesterone in 13-month-old prepubertal Nellore heifers: effects on in vitro embryo production and pregnancy rate - Letícia Padovani da Silva; Marina de Oliveira Silva; Marcelo Sant’Ana Borges; Jaine Martelo Pagoto; Yeda Fumie Watanabe; Clara Slade Oliveira; Maria Eugênia Zerlotti Mercadante; Fabio Morato Monteiro (Tropical Animal Health and Production, 2024)

Long-term trends (1986–2019) in the physicochemical properties of the Sado Estuary (Portugal) driven primarily by changes in river flow and influenced by marine upwelling - Beatriz Biguino; Carlos Antunes; João Miguel Dias; Ivan D. Haigh; Joana P.C. Cruz; Carlos Borges; Carla Palma; Humberto Pereira; Ana Picado; Afonso Ferreira; Ana C. Brito (Marine Pollution Bulletin, 2024)

Assessment In vitro and In silico of the Activity of Thiadiazines as NorA Efflux Pump Inhibitors - Ana Carolina Justino de Araújo; Priscilla Ramos Freitas; Isaac Moura Araújo; João Arthur de Oliveira Borges; Sheila Alves Gonçalves; Cícera Laura Roque Paulo; Ray Silva Almeida; Cícera Datiane de Moraes Oliveira-Tintino; José Bezerra de Araújo-Neto; Igor José dos Santos Nascimento; João Xavier de Araújo-Júnior; Edeildo Ferreira da Silva-Júnior; et al. (Current Microbiology, 2024)

Chemical and visual stimuli for conservation biological control of stink bugs in soybean: potential use and flaws on egg parasitoid recruitment - Ana Carolina G. Lagôa; Pedro H. B. Togni; Michely F. Aquino; Maria Carolina Blassioli-Moraes; Miguel Borges; Raúl A. Laumann (BioControl, 2024)

Generating insights to improve the performance of communities supported agriculture: an analysis focused on female participation, governance structure and volume of food distributed - Gustavo Alves de Melo; Maria Gabriela Mendonça Peixoto; Samuel Borges Barbosa; Ana Júlia Silva Alves; Anna Clara Lasso Souza; Maria Cristina Angélico Mendonça; Luiz Gonzaga de Castro Júnior; Patrícia Guarnieri dos Santos; André Luiz Marques Serrano; Clóvis Neumann (Environment, Development and Sustainability, 2024)

Minor loss or huge threat? Assessment of potential infrastructure projects reveals drastic landscape degradation in the Atlantic forest - Jéssica Stéfane Alves Cunha; Nathan Castro Fonsêca; Cinthia Renata Vieira de Lima; Jhonathan Gomes dos Santos; Herbert de Tejo Pereira; Bruna Martins Bezerra; Ana Carolina Borges Lins-e-Silva (Journal for Nature Conservation, 2024)

Morpho-anatomical adaptations of Centella asiatica (Apiaceae) in different coastal sand microenvironments of Restinga and in an urbanized area - Calebe Borges; Makeli Garibotti Lusa; Amanda Baldessar; Guilherme Almeida Garcia Rodrigues; Ana Claudia Rodrigues (Flora, 2024)

Drug to genome to drug: a computational large-scale chemogenomics screening for novel drug candidates against sporotrichosis - Andressa Santana Santos; Vinícius Alexandre Fiaia Costa; Vivianny Aparecida Queiroz Freitas; Laura Raniere Borges dos Anjos; Eder Soares de Almeida Santos; Thales Domingos Arantes; Carolina Rodrigues Costa; Ana Laura de Sene Amâncio Zara; Maria do Rosário Rodrigues Silva; Bruno Junior Neves (Brazilian Journal of Microbiology, 2024)

Inception of Constructional Submarine Conduit by Asymmetry Generated by Turbidity Current - Daniel Bayer da Silva; Eduardo Puhl; Rafael Manica; Ana Luiza de Oliveira Borges; Adriano Roessler Viana (Journal of Marine Science and Engineering, 2024)
Submarine conduits are features responsible for transporting clastic debris from continents to the deep ocean. While the architecture of conduits has been extensively studied, the process of their inception remains unclear. This study highlights the possibility that some conduits are initiated by depositional processes involving turbidity currents. Here, we present the results of eight experiments where gravity currents were allowed to develop their own pathways. The simulation tank represented natural scales of continental shelves, slopes, and basins. The initial experiments involved sediment-laden flows with low density (1–10% in volume). In first experiment runs (Series I), sediment deposition occurred primarily on the shelf and slope, resulting in an asymmetric transverse profile. This asymmetry facilitated subsequent conservative currents (1034 to 1070 kg/m3 due to salt dissolution) flowing alongside during the second series, resulting in the formation of a constructive submarine conduit. This feature is analogous to gully formations observed in various locations. This study correlates these findings with gully-like features and proposes a model where non-confined density flows can evolve into confined flows through the construction of asymmetric topography. An evolutionary model is proposed to explain the mechanism, which potentially elucidates the formation of many submarine conduits.

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Retrospective application of ICH M7 to anti-hypertensive drugs in Brazil: Risk assessment of potentially mutagenic impurities - Fernanda Waechter; Antonio Anax Falcao Oliveira; Ana Lucia Borges Shimada; Edson Bernes Junior; Elizabeth de Souza Nascimento (Regulatory Toxicology and Pharmacology, 2024)

Partitioning of water vapor and CO fluxes and underlying water use efficiency evaluation in a Brazilian seasonally dry tropical forest (Caatinga) using the Fluxpart model - Camilla K. Borges; Rayonil G. Carneiro; Cleber A. Santos; Marcelo Zeri; Patryk Poczta; Ana Paula M.A. Cunha; Iwona S. Stachlewska; Carlos A.C. dos Santos (Journal of South American Earth Sciences, 2024)

Neurological aspects of HTLV-1 infection: symptoms in apparently asymptomatic carriers - Qesya Rodrigues Ferreira; Ana Flávia Novaes; Carolina Souza Santana; Arthur Shigueru Umeda; Jéssica Oliveira de Souza Nascimento; João Pedro Melo de Freitas Santos; Larissa Alves Fernandes; Matheus Nascimento Moura; Rebeca Leão Amorim; Vinícius Nogueira Cavalcanti; Ariana Leal Borges da Cruz; Fernanda Khouri Barreto; et al. (Journal of NeuroVirology, 2024)

Experimental and modeling of potassium diclofenac uptake on activated carbon - Cristiane Ferraz de Azevedo; Nicholas Fernandes de Souza; Frantchescole Borges Cardoso; Ana Carolina Ferreira Piazzi Fuhr; Eder Claudio Lima; Alice Gonçalves Osório; Fernando Machado Machado (Environmental Science and Pollution Research, 2024)

Recent advances in nanomaterial-based optical biosensors for food safety applications: Ochratoxin-A detection, as case study - Diana I. Meira; Ana I. Barbosa; Joel Borges; Rui L. Reis; Vitor M. Correlo; Filipe Vaz (Critical Reviews in Food Science and Nutrition, 2024)

Unveiling the reproduction of Proteopsis argentea (Asteraceae): how the complex pollination system might influence its conservation status - João Paulo Raimundo Borges; Ilmara Aparecida Oliveira Ferreira; Danubia Natalina Silva; Cinthia Soares Novaes; Ana Carolina Pereira Machado; Gudryan Jackson Baronio; Leonardo Ré Jorge; André Rodrigo Rech (Brazilian Journal of Botany, 2024)

Phytochemical composition of aerial parts and roots of Pfaffia glomerata (Spreng.) Pedersen and anticholinesterase, antioxidant, and antiglycation activities - Rodrigo Rodrigues Franco; Rafaella Martins Franco; Allisson Benatti Justino; Ana Luiza Silva Borges; Vinícius Prado Bittar; Natieli Saito; André Lopes Saraiva; Nilson Nicolau Júnior; Wagner Campos Otoni; Foued Salmen Espindola (Protoplasma, 2024)

Ecotoxicological strategies employing biochemical markers and organisms to monitor the efficacy of malathion photolysis treatment - Rafaela Imoski; Laís Jarenko da Cruz; Angela Maria Palacio-Cortés; Ana Marta Schafaschek; Eric Schwamberger; Pamella Regina Mariotti; Andre Luis Bichibichi Borges; Fernando Rodrigues-Silva; Liziê Daniela Tentler Prola; Mario Antônio Navarro da Silva; Adriane Martins de Freitas; Marcus Vinicius de Liz (Chemosphere, 2024)

Supplemental vibrissal extensions as an alternative to improve the tactile sensitivity of blind dogs – a preliminary approach investigation - Manuella Oliveira Borges de Sampaio; Fabiano Montiani-Ferreira; Franz Riegler Mello; Camila Bolmann Martins; Ana Leticia Groszewicz de Souza; Mariza Bortolini; Paulo Roberto Klaumann; Bret A. Moore (Veterinary Research Communications, 2024)

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

A fermented milk drink with Umbu (Spondias tuberosa) pulp and whey is effective for weight gain and re-nutrition in malnourished: An in vivo study in mice and children - Gabriela da Rocha Lemos Mendes; Handray Fernandes de Souza; João Pedro Antunes Lopes; Ana Carolina Santos Rocha; Raquel Borges Faria; Fábio Ribeiro dos Santos; Bruna Mara Aparecida de Carvalho de Mesquita; Sérgio Henrique Sousa Santos; Carla Adriana Ferreira Durães; Sildimar Rodrigues Ferreira; Sarah Caroline Oliveira de Souza Boitrago; Jéssica Santos Leal; et al. (Food Research International, 2024)

Prey consumption and conversion efficiency in females of two feral populations of Macrolophus pygmaeus, a biocontrol agent of Tuta absoluta - Isabel Borges; Luísa Oliveira; Francisco Barbosa; Elisabete Figueiredo; José Carlos Franco; Ana C. Durão; António Onofre Soares (Phytoparasitica, 2024)
Macrolophus pygmaeus (Rambur, 1839) (Hemiptera: Miridae) is a polyphagous predator used in programs of biological control and integrated pest management as a natural enemy against small arthropod pests including whiteflies, thrips, spider mites and aphid. This mirid is also successfully mass reared under factitious prey for commercial purposes. In the present study we assessed and compared the prey consumption, weight gain and conversion efficiency in females of two populations of M. pygmaeus , from mainland Portugal and the Azores, fed on single prey diets of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) eggs, or Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) eggs. We found that female’s prey consumption on eggs of T. absoluta was higher than that of E. kuehniella , presumably due to the comparative size/amount of biomass of the eggs. Translating prey consumption in biomass ingested, we only found a significant difference for consumption on E. kuehniella eggs by M. pygmaeus from the Azores. Despite the smaller size of females from the Azores, they were able to consume more prey and ultimately reaching a similar body weight and conversion efficiency compared with females from mainland, independently of the prey provided. Our results are in line with a previous study, showing differences in the life-history traits of M. pygmaeus from mainland Portugal and Azorean populations fed on alternative prey. From an applied perspective, our results are a contribution to the decision-making on the use of the most effective biocontrol agents for different prey and/or agroecosystem contexts.

Prior denaturation and aggregation of whey proteins: is this a useful strategy for increasing the content of these proteins in UHT high-protein dairy beverages? - Alisson Borges de Souza; Ana Augusta Odorissi Xavier; Rodrigo Stephani; Guilherme M. Tavares (Food and Bioproducts Processing, 2024)

Chronic exposure to 2,2′-azobis-2-amidinopropane that induces intestinal damage and oxidative stress in larvae of Drosophila melanogaster - Rener Mateus Francisco Duarte; Serena Mares Malta; Fernanda Naves Araújo do Prado Mascarenhas; Vinicius Prado Bittar; Ana Luiza Borges; Renata Roland Teixeira; Renata Graciele Zanon; Carlos Ueira Vieira; Foued Salmen Espindola (Environmental Toxicology and Pharmacology, 2024)

Dose–Response Effect of Saccharomyces cerevisiae UFMG A-905 on the Prevention of Asthma in an Animal Model - Thamires M. S. Milani; Camila M. Sandy; Ana Paula Carvalho Thiers Calazans; Rosana Q. Silva; Vanessa M. B. Fonseca; Flaviano S. Martins; Marcos C. Borges (Probiotics and Antimicrobial Proteins, 2024)

Update on Brazilian essential oils with leishmanicidal activity - Ingrid Borges Siqueira; Yvanna Louise Di Christine Oliveira; Sona Jain; Audrey Rouse Soares Tavares Silva; Luiz Fernando de Jesus Nascimento; Márcio Luiz da Gama Lisboa; Tiago Branquinho Oliveira; Damião Pergentino de Sousa; Ana Andrea Teixeira Barbosa; Silvio Santana Dolabella (Phytochemistry Reviews, 2024)

Relationship between age, scrotal circumference, postweaning weight and semen quality in Nellore and Caracu bulls: a cross sectional study - Jaine Martelo Pagoto; Lorena Ferreira Benfica; Marcelo Sant’Ana Borges; Viviane Andrade Ligori; Roberta Carrilho Canesin; Maria Eugênia Zerlotti Mercadante; Fabio Morato Monteiro (Tropical Animal Health and Production, 2023)

Evaluation of berberine nanoparticles as a strategy to modulate acetylcholinesterase activity - Fernanda Vitória Leimann; Luma Borges de Souza; Byanca Pereira Moreira de Oliveira; Bruna Franzon Rossi; Patrícia Sabino da Silva; Carlos Seiti Hurtado Shiraishi; Vanessa Kaplum; Rui Miguel Abreu; Carla Pereira; Lillian Barros; Ana Paula Peron; Rafael Porto Ineu; et al. (Food Research International, 2023)

Reproductive Behavior and Stridulatory Communication in Sternochetus mangiferae (Coleoptera: Curculionidae: Cryptorhynchinae) - Giancarlo Catafesta; Maria Carolina Blassioli-Moraes; Miguel Borges; Ana Cristina Meneses Mendes Gomes; Alessandra de Carvalho Silva; Marcelo Perrone Ricalde; Raúl Alberto Laumann (Journal of Insect Behavior, 2023)

Anthropic Impact on the Critically Endangered Melanophryniscus admirabilis (Admirable Redbelly Toad): Evidence from the Presence of Multiresistant Enterobacteriaceae - Julia Ienes-Lima; Janira Prichula; Michelle Abadie; Márcio Borges-Martins; Ana Paula Guedes Frazzon (Current Microbiology, 2023)

Biopolymers Synthesized by Microalgae Grown in Wastewater: a Technological Survey - Ana Victória dos Santos Borges; Bianca Bomfim Andrade; Jamille Santos Santana; Ravena Maria de Almeida Medeiros; Carolina Oliveira de Souza; Denilson de Jesus Assis; Jania Betania Alves da Silva; Pedro Paulo Lordelo Guimarães Tavares; Lucas Guimarães Cardoso (BioEnergy Research, 2023)

Nanoencapsulation of Curcuma longa L. extract for the treatment of experimental colitis - Débora dos Anjos Weber Luz; Ana Paula de Santi Rampazzo; Stephanie Carvalho Borges; Camila Quaglio Neves; Priscila Dayane de Freitas Santos; Nilza Cristina Buttow; Cassiano Pires; Rilton Alves de Freitas; Ciomar Aparecida Bersani Amado; Odinei Hess Gonçalves; Maria Raquel Marçal Natali (Food Bioscience, 2023)

Repurposing miconazole and tamoxifen for the treatment of Mycobacterium abscessus complex infections through in silico chemogenomics approach - Laura Raniere Borges dos Anjos; Vinícius Alexandre Fiaia Costa; Bruno Junior Neves; Ana Paula Junqueira-Kipnis; André Kipnis (World Journal of Microbiology and Biotechnology, 2023)

The dangerous link between coal dust exposure and DNA damage: unraveling the role of some of the chemical agents and oxidative stress - Alvaro Miranda-Guevara; Amner Muñoz-Acevedo; Ornella Fiorillo-Moreno; Antonio Acosta-Hoyos; Leonardo Pacheco-Londoño; Milton Quintana-Sosa; Yurina De Moya; Johnny Dias; Guilherme Soares de Souza; Wilner Martinez-Lopez; Ana Letícia Hilário Garcia; Juliana da Silva; et al. (Environmental Geochemistry and Health, 2023)
Exposure to coal mining dust poses a substantial health hazard to individuals due to the complex mixture of components released during the extraction process. This study aimed to assess the oxidative potential of residual coal mining dust on human lymphocyte DNA and telomeres and to perform a chemical characterization of coal dust and urine samples. The study included 150 individuals exposed to coal dust for over ten years, along with 120 control individuals. The results revealed significantly higher levels of DNA damage in the exposed group, as indicated by the standard comet assay, and oxidative damage, as determined by the FPG-modified comet assay. Moreover, the exposed individuals exhibited significantly shorter telomeres compared to the control group, and a significant correlation was found between telomere length and oxidative DNA damage. Using the PIXE method on urine samples, significantly higher concentrations of sodium (Na), phosphorus (P), sulfur (S), chlorine (Cl), potassium (K), iron (Fe), zinc (Zn), and bromine (Br) were observed in the exposed group compared to the control group. Furthermore, men showed shorter telomeres, greater DNA damage, and higher concentrations of nickel (Ni), calcium (Ca), and chromium (Cr) compared to exposed women. Additionally, the study characterized the particles released into the environment through GC–MS analysis, identifying several compounds, including polycyclic aromatic hydrocarbons (PAHs) such as fluoranthene, naphthalene, anthracene, 7H-benzo[c]fluorene, phenanthrene, pyrene, benz[a]anthracene, chrysene, and some alkyl derivatives. These findings underscore the significant health risks associated with exposure to coal mining dust, emphasizing the importance of further research and the implementation of regulatory measures to safeguard the health of individuals in affected populations. Graphic abstract

Selective versus strategic control against Rhipicephalus microplus in cattle: A comparative analysis of efficacy, animal health, productivity, cost, and resistance management - João Eduardo Nicaretta; Rubens Dias de Melo Junior; Raphaela Barbosa Naves; Igor Maciel Lopes de Morais; Vanessa Ferreira Salvador; Luccas Lourenzzo Lima Lins Leal; Ana Lucia Coutinho Teixeira; Lorena Lopes Ferreira; Guilherme Marcondes Klafke; Caio Marcio de Oliveira Monteiro; Fernando de Almeida Borges; Livio Martins Costa Junior; et al. (Veterinary Parasitology, 2023)

The Landscape of Neutralizing Monoclonal Antibodies (nAbs) for Treatment and Prevention of COVID-19 - Aline de Almeida Oliveira; Diana Praia Borges Freire; Ana Rodrigues de Andrade; Amanda de Miranda Marques; Luciana da Silva Madeira; José Procópio Moreno Senna; Ivna Alana Freitas Brasileiro da Silveira; Beatriz de Castro Fialho (Journal of Pharmaceutical Innovation, 2023)
Purpose After nearly 3 years of the COVID-19 pandemic, even though a vast body of knowledge and products (including vaccines and treatments) have been developed and disseminated, the virus is still evolving and new variants arising. Consequently, thousands of lives continue to be lost. Neutralizing monoclonal antibodies (nAbs) are promising drugs that emerged to treat SARS-CoV-2. In the uncertainty of the current situation, there is the question of whether organizations should continue to invest in this technology. To help decision-making in scientifical and pharmaceutical organizations, it is of major importance to monitor the development of products and technologies. Therefore, the aim of this study is analyze the landscape of nAbs for COVID-19. Methods The scenario of 473 biotherapeutics focusing on nAbs was evaluated using foresight techniques and a review of literature. Data were obtained from structured and semi-structured databases and processed for treatment, cleaning, consistency, validation, and enrichment. Results We identified 227 nAbs and performed an extensive literature review of 16 nAbs in late clinical development, including development technologies, responses to variants of concern (VOCs), manufacturing, and clinical aspects. Conclusions Even though the emergence of new VOCs is a threat to the effectiveness of this treatment, demanding constant genomic surveillance, the use of nAbs to treat and prevent COVID-19 will probably continue to be relevant due to excellent safety profiles and the possibility of immediate immunity transfer, especially in patients showing inadequate immunological response to vaccination. Therefore, we suggest that organizations should keep investing in improvements in this technology.

Genetic Analysis of LigA, LipL32, Loa22, and OmpL1 Antigens from Leptospira spp. Sejroe Serogroup: How Close We Are To a Vaccine Against Bovine Leptospirosis? - Maria Isabel Nogueira Di Azevedo; Ana Luiza dos Santos Baptista Borges; Frederico Kremer; Juliana dos Santos Loria de Melo; Filipe Anibal Carvalho-Costa; Walter Lilenbaum (Current Microbiology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Correction: Flavonoid as possible therapeutic targets against COVID-19: a scoping review of in silico studies - Larissa Toigo; Emilly Isabelli dos Santos Teodoro; Ana Carolina Guidi; Naiara Cássia Gancedo; Marcus Vinícius Petruco; Eduardo Borges Melo; Fernanda Stumpf Tonin; Fernando Fernandez-Llimos; Danielly Chierrito; João Carlos Palazzo de Mello; Daniela Cristina de Medeiros Araújo; Andréia Cristina Conegero Sanches (DARU Journal of Pharmaceutical Sciences, 2023)

Larvicidal potential of extracts and isolated compounds from Piper cubeba fruits against Aedes aegypti (Diptera: Culicidae) larvae - Ana Carolina Gomes; Alexandre Borges; Daniela Garcia Zoca; Marcio Luís Andrade e Silva; Aline Rafaela da Silva Rodrigues Machado; Alex Martins Machado; Mario F. C. Santos; Rosangela da Silva de Laurentiz (Natural Product Research, 2023)

Sperm head morphometry and chromatin alterations in bulls with different conception rates - José Andrés Nivia Riveros; Isabelle Cristina Pereira; Ana Carolina Bahia Teixeira; Juliana Horta Wilke Diniz; Alan Maia Borges; Juan Felipe García Díaz; Marcelo Emílio Beletti; Leticia Zoccolaro Oliveira (Animal Reproduction Science, 2023)

Clozapine-loaded nanocapsules improve antipsychotic activity in rats: building a sequential PopPK/PD model to discriminate nanocarriers in the preformulation step - Ana Cláudia Funguetto-Ribeiro; Tamara Ramos Maciel; Annelize Gruppi Lunardi; Daniel Borges Gomes; Manuel Ibarra; Sandra Elisa Haas (Pharmaceutical Research, 2023)

Scientific literature on freshwater ecosystem services: trends, biases, and future directions - João Carlos Nabout; Karine Borges Machado; Ana Clara Maciel David; Laura Beatriz Gomes Mendonça; Samiris Pereira da Silva; Priscilla Carvalho (Hydrobiologia, 2023)

Rhomb-I, a P–I metalloproteinase from Lachesis muta rhombeata venom degrades vessel extra cellular matrix components and impairs platelet aggregation - Valéria Gonçalves de Alvarenga; Luciana S. Oliveira; Gustavo O. Santos; Dan E. Vivas-Ruiz; Márcia Helena Borges; Rodrigo C.G. de Souza; Johannes A. Eble; Ana Maria Moura-da-Silva; Eladio F. Sanchez (Toxicon, 2023)

Partial characterization of Loxosceles anomala (Mello-Leitão, 1917) venom: A brown spider of potential medical concern - Pamella Peres-Damásio; Rafaela Silva-Magalhães; Ana Luiza Silva-Araújo; Elaine Henriques Teixeira Pereira; Adriano Lima Silveira; Luana Silveira da Rocha Nowicki Varella; Márcia Helena Borges; Carlos Chavez-Olórtegui; Ana Luiza Bittencourt Paiva; Clara Guerra-Duarte (Toxicon, 2023)

Extruded urea levels in lamb supplementation in rainy tropical savanna conditions: the triad host-gastrointestinal nematodes-environment - Francisca Fernanda da Silva Roberto; Gelson dos Santos Difante; Roberto Germano Costa; Fernando de Almeida Borges; Luis Carlos Vinhas Ítavo; Camila Celeste Brandão Ferreira Ítavo; Neila Lidiany Ribeiro; Jéssica Gomes Rodrigues; Marislayne de Gusmão Pereira; Gabriela Oliveira de Aquino Monteiro; Emmanuel Lievio de Lima Véras; Antonio Leandro Chaves Gurgel; et al. (Tropical Animal Health and Production, 2023)

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Brazilian Semiarid Bradyrhizobium Strains Increase Nitrogen Accumulation and Modulate Physiological Parameters to Enable Superior Grain Production in Soybean Genotypes - Luis Borges Rocha; Elaine Martins da Costa; Ana Clara Martins de Sousa Ribeiro; Jasmine Ferreira dos Santos; Rafael de Souza Miranda; Amanda Soares Santos; Stelamaris de Oliveira Paula-Marinho; Bruno Sousa Figueiredo da Fonseca; Fatima Maria de Souza Moreira (Journal of Soil Science and Plant Nutrition, 2023)

Is the São Francisco River a historical barrier to gene flow for populations of Melipona mandacaia Smith, 1863 (Hymenoptera: Apidae)? - Leydiane da Conceição Lazarino; Lorena Andrade Nunes; Sâmela Silva Mendes; Armanda Borges Pinto; Matheus Galvão Brito; Juvenal Cordeiro Silva Junior; Christine Steiner São Bernardo; Ana Maria Waldschmidt (Journal of Insect Conservation, 2023)

Response of phytoplankton to coastal upwelling: The importance of temporal and spatial scales - Luciane Favareto; Vanda Brotas; Natalia Rudorff; Nuno Zacarias; Andreia Tracana; Luisa Lamas; Ângela Nascimento; Afonso Ferreira; Mara Gomes; Carlos Borges; Carla Palma; Ana C. Brito (Limnology and Oceanography, 2023)
The Western Iberian Coast (WIC) is characterized by a dynamic coastal upwelling system with interactions between oceanographic features and continental river run‐off. The present study investigates the spatio‐temporal variability in the concentrations of Chlorophyll a (Chl a ) and turbidity, and their relationships with physical and other biogeochemical properties along the entire coast of Portugal, as well as the response of phytoplankton to coastal upwelling pulses. In situ data were obtained during four oceanographic campaigns conducted in spring (April–May 2019), autumn (October 2018 and 2019), and early spring (February–March 2020). Upwelling conditions were evaluated through an upwelling index and auxiliary data such as sea surface temperature and height. In the WIC, the in situ surface temperature and salinity have a clear spatial pattern, both increasing from North to South. In autumn 2018 the highest temperatures coincided with the weakening of spring–summer upwelling conditions. Overall, high Chl a was associated with lower temperatures and higher dissolved oxygen concentrations (e.g., spring 2019). During spring 2019, an increase in Chl a , especially in the northern area, was associated with previous upwelling conditions. In early spring 2020, ongoing upwelling conditions in the northern area were associated with high turbidity and nutrients close to the shoreline with no immediate biological responses. An increase in Chl a was visible in satellite imagery a few days later. These results highlight the importance of understanding the complexity of coastal processes in the WIC.

Flavonoid as possible therapeutic targets against COVID-19: a scoping review of in silico studies - Larissa Toigo; Emilly Isabelli dos Santos Teodoro; Ana Carolina Guidi; Naiara Cássia Gancedo; Marcus Vinícius Petruco; Eduardo Borges Melo; Fernanda Stumpf Tonin; Fernando Fernandez-Llimos; Danielly Chierrito; João Carlos Palazzo de Mello; Daniela Cristina de Medeiros Araújo; Andréia Cristina Conegero Sanches (DARU Journal of Pharmaceutical Sciences, 2023)

Source apportionment of PM2.5 before and after COVID-19 lockdown in an urban-industrial area of the Lisbon metropolitan area, Portugal - Carla A. Gamelas; Nuno Canha; Ana Vicente; Anabela Silva; Sónia Borges; Célia Alves; Zsofia Kertesz; Susana Marta Almeida (Urban Climate, 2023)

How to use human biomonitoring in chemical risk assessment: Methodological aspects, recommendations, and lessons learned from HBM4EU - Tiina Santonen; Selma Mahiout; Paula Alvito; Petra Apel; Jos Bessems; Wieneke Bil; Teresa Borges; Stephan Bose-O'Reilly; Jurgen Buekers; Ana Isabel Cañas Portilla; Argelia Castaño Calvo; Mercedes de Alba González; et al. (International Journal of Hygiene and Environmental Health, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

An update on the development of antiviral against Mayaro virus: from molecules to potential viral targets - Marina Paschoalino; Mikaela dos Santos Marinho; Igor Andrade Santos; Victória Riquena Grosche; Daniel Oliveira Silva Martins; Rafael Borges Rosa; Ana Carolina Gomes Jardim (Archives of Microbiology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

A technological approach using a metal-free immobilized photocatalyst for the removal of pharmaceutical substances from urban wastewaters - Maria J. Sampaio; Ana R.L. Ribeiro; Cláudia M.R. Ribeiro; Rita A. Borges; Marta F. Pedrosa; Adrián M.T. Silva; Cláudia G. Silva; Joaquim L. Faria (Chemical Engineering Journal, 2023)

Fast Identification Method for Screening Bacteria from Faecal Samples Using Oxford Nanopore Technologies MinION Sequencing - Ana Sofia G. Borges; Meghna Basu; Erik Brinks; Corinna Bang; Gyu-Sung Cho; John F. Baines; Andre Franke; Charles M. A. P. Franz (Current Microbiology, 2023)
Most bacterial identification methods require extensive culturing, strain purification and DNA extraction protocols. This leads to additional expenses and time lags when isolating specific bacteria from complex microbiological ecosystems. This study aimed to develop a fast and robust method for identification of lactobacilli, bifidobacteria and Bacteroides in human faecal samples. Bacteria from faecal samples were cultured anaerobically on selective media. Sonication-based DNA extraction was performed, followed by almost complete 16S rRNA gene polymerase chain reaction amplification and MinION sequencing with the Flongle adapter. Sequence analysis was performed using NanoCLUST, while RStudio was used for graphics. For 110 of the 125 colonies investigated, 100% of reads were attributed to a single species, while the remaining 15 colonies consisted of mixtures of up to three different species. The proposed bacterial identification method is advantageous for isolating particular bacteria for which there are no exclusively selective media, as it avoids lengthy colony purification and DNA purification methods, and yields a quick colony identification with high accuracy. Therefore, this method can be used for directly screening for pure cultures of target microorganisms and is suitable for the identification of bacteria in culturomics studies.

Potential in vitro action of an adenosine analog and synergism with penicillin against Corynebacterium pseudotuberculosis - Pedro Negri Bernardino; Carolina Lechinski de Paula; Ana Flávia Marques Pereira; Márcio Garcia Ribeiro; Vasco Ariston de Carvalho Azevedo; Alexandre Secorun Borges; Ary Fernandes-Júnior; José Paes Oliveira-Filho (Brazilian Journal of Microbiology, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Canine distemper virus and canine adenovirus type 1 co-infection in a free-living hoary fox (Lycalopex vetulus) from Brazil - Maraya Lincoln Silva; Mayara Grego Caiaffa; André Luiz Mota da Costa; Rodrigo Hidalgo Friciello Teixeira; Ticiana Brasil Ervedosa; Eduardo Ferreira Machado; Pedro Enrique Navas Suárez; Rodrigo Albergaria Réssio; Cinthya Cirqueira Borges; Isis Paixão de Jesus; Julia de Carvalho; Ketlyn Bolsachini Figueiredo; et al. (Brazilian Journal of Microbiology, 2023)

Pinnipeds carriers of pathogenic Leptospira: New data based on molecular characterization - Felipe D'Azeredo Torres; Ana Luiza dos Santos Baptista Borges; Cristiane Kolesnikovas; Camila Domit; Carla Beatriz Barbosa; Filipe Anibal Carvalho-Costa; Maria Isabel Nogueira Di Azevedo; Walter Lilenbaum (Research in Veterinary Science, 2023)

Identification of sustainable practices applied to ship recycling - Júlia Fernandes Sant’ Ana; Alvim Borges da Silva Filho; Newton Narciso Pereira (Journal of Cleaner Production, 2023)

Sedimentation in UHT high-protein dairy beverages: Influence of sequential preheating coupled with homogenisation or supplementation with carbohydrates - Alisson Borges de Souza; Ana Augusta O. Xavier; Rodrigo Stephani; Guilherme M. Tavares (International Dairy Journal, 2023)

Secondary succession in swamp gallery forests along 65 fallow years after shifting cultivation - Sílvia Laine Borges; Maxmiller Cardoso Ferreira; Bruno Machado Teles Walter; Ana Carla dos Santos; Aldicir Osni Scariot; Isabel Belloni Schmidt (Forest Ecology and Management, 2023)

Corrigendum to “The impact of long-term weather changes on air quality in Brazil” [J. Atmos. Environ. 283 (2022) 119182] - Francisco Jablinski Castelhano; Ana Clara Neme Pedroso; Igor Cobelo; Rafael Borge; Henrique L. Roig; Matthew Adams; Heresh Amini; Petros Koutrakis; Weeberb J. Réquia (Atmospheric Environment, 2023)

A roadmap for ladybird conservation and recovery - António O. Soares; Danny Haelewaters; Olga M. C. C. Ameixa; Isabel Borges; Peter M. J. Brown; Pedro Cardoso; Michiel D. de Groot; Edward W. Evans; Audrey A. Grez; Axel Hochkirch; Milada Holecová; Alois Honěk; et al. (Conservation Biology, 2023)
Ladybirds (Coleoptera: Coccinellidae) provide services that are critical to food production, and they fulfill an ecological role as a food source for predators. The richness, abundance, and distribution of ladybirds, however, are compromised by many anthropogenic threats. Meanwhile, a lack of knowledge of the conservation status of most species and the factors driving their population dynamics hinders the development and implementation of conservation strategies for ladybirds. We conducted a review of the literature on the ecology, diversity, and conservation of ladybirds to identify their key ecological threats. Ladybird populations are most affected by climate factors, landscape composition, and biological invasions. We suggest mitigating actions for ladybird conservation and recovery. Short‐term actions include citizen science programs and education, protective measures for habitat recovery and threatened species, prevention of the introduction of non‐native species, and the maintenance and restoration of natural areas and landscape heterogeneity. Mid‐term actions involve the analysis of data from monitoring programs and insect collections to disentangle the effect of different threats to ladybird populations, understand habitat use by taxa on which there is limited knowledge, and quantify temporal trends of abundance, diversity, and biomass along a management‐intensity gradient. Long‐term actions include the development of a worldwide monitoring program based on standardized sampling to fill data gaps, increase explanatory power, streamline analyses, and facilitate global collaborations.

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Increased oyster aquaculture in the Sado Estuary (Portugal): How to ensure ecosystem sustainability? - Ana C. Brito; Humberto Pereira; Ana Picado; Joana Cruz; Rui Cereja; Beatriz Biguino; Paula Chainho; Ângela Nascimento; Frederico Carvalho; Sara Cabral; Cátia Santos; Carla Palma; et al. (Science of The Total Environment, 2023)

The neurotoxic mechanism of Jack Bean Urease in insects involves the interplay between octopaminergic and dopaminergic pathways - Yuri Correia Barreto; Raquel Soares Oliveira; Bruna Trindade Borges; Maria Eduarda Rosa; Ana Paula Zanatta; Carlos Gabriel Moreira de Almeida; Lúcia Vinadé; Celia Regina Carlini; Cháriston André Dal Belo (Pesticide Biochemistry and Physiology, 2023)

Cellular Aging Secretes: a Comparison of Bone-Marrow-Derived and Induced Mesenchymal Stem Cells and Their Secretome Over Long-Term Culture - Ana Marote; Diogo Santos; Bárbara Mendes-Pinheiro; Cláudia Serre-Miranda; Sandra I. Anjo; Joana Vieira; Filipa Ferreira-Antunes; Joana Sofia Correia; Caroline Borges-Pereira; Andreia G. Pinho; Jonas Campos; Bruno Manadas; et al. (Stem Cell Reviews and Reports, 2023)

Sericin Biofilm Endowed with Silver Sulfadiazine for Treatment of Burns - Ana Paula Sone; Marcelino Luiz Gimenes; Tatiana Shioji Tiuman; Jaqueline Hoscheid; Getulio Capello Tominc; Mariana Dalmagro; Eduardo Borges Lied; Camilo Freddy Mendoza Morejon (Journal of Pharmaceutical Innovation, 2022)

CD14 signaling mediates lung immunopathology and mice mortality induced by Achromobacter xylosoxidans - Jefferson Elias-Oliveira; Morgana Kelly Borges Prado; Camila Oliveira Silva Souza; Marcella Roverato Pastore; Simone Gusmão Ramos; Ana Lúcia Costa Darini; Luiz Gustavo Gardinassi; Lúcia Helena Faccioli (Inflammation Research, 2022)

Erysipelas in a stranded common bottlenose dolphin: first report in a South American odontocete - Carlos Sacristán; Ana Carolina Ewbank; Angélica María Sánchez-Sarmiento; Aricia Duarte-Benvenuto; João Carlos Gomes Borges; Vanessa Araújo Rebelo; Josué Díaz-Delgado; Lara Borges Keid; José Luiz Catão-Dias (Brazilian Journal of Microbiology, 2022)

Induced Stress and Tactile Stimulation Applied to Primiparous does and their Consequences on Maternal Behavior, Human-Animal Relationships, and Future Offspringˊs Sexual Disorders - Angela C. F. Oliveira; Luiza M. Bernardi; Ana Larissa B. Monteiro; Kassy G. Silva; Saulo H. Weber; Tâmara D. Borges; Antoni Dalmau; Leandro B. Costa (Veterinary Research Communications, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Effects of different probiotic strains B. lactis, L. rhamnosus and L. reuteri on brain-intestinal axis immunomodulation in an endotoxin-induced inflammation - Monique Michels; Gabriel Fernandes Alves Jesus; Mariane Rocha Abatti; Emily Córneo; Luana Cucker; Heloisa de Medeiros Borges; Natan da Silva Matos; Luana Bezerra Rocha; Rodrigo Dias; Carla Sasso Simon; Ana Paula Lorenzen Voytena; Marina Rossetto; et al. (Molecular Neurobiology, 2022)

Endophytic fungi of Brunfelsia uniflora: isolation, cryopreservation, and determination of enzymatic and antioxidant activity - Sara Jane Marsola; Lais Freitas Jorge; Adriano Borges Meniqueti; Miria Benetati Delgado Bertéli; Thaís Emanuelle Feijó de Lima; José Luiz Bezerra; Ana Daniela Lopes; Zilda Cristiani Gazim; Juliana Silveira do Valle; Nelson Barros Colauto; Giani Andrea Linde (World Journal of Microbiology and Biotechnology, 2022)

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Detecting the attack of the fall armyworm (Spodoptera frugiperda) in cotton plants with machine learning and spectral measurements - Ana Paula Marques Ramos; Felipe David Georges Gomes; Mayara Maezano Faita Pinheiro; Danielle Elis Garcia Furuya; Wesley Nunes Gonçalvez; José Marcato Junior; Mirian Fernandes Furtado Michereff; Maria Carolina Blassioli-Moraes; Miguel Borges; Raúl Alberto Alaumann; Veraldo Liesenberg; Lúcio André de Castro Jorge; et al. (Precision Agriculture, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Transposable elements expression in Rhinella marina (cane toad) specimens submitted to immune and stress challenge - Adriana Ludwig; Michelle Orane Schemberger; Camilla Borges Gazolla; Joana de Moura Gama; Iraine Duarte; Ana Luisa Kalb Lopes; Carolina Mathias; Desirrê Alexia Lourenço Petters-Vandresen; Michelle Louise Zattera; Daniel Pacheco Bruschi (Genetica, 2021)

Habitat filtering and inferred dispersal ability condition across‐scale species turnover and rarity in Macaronesian island spider assemblages - Jagoba Malumbres‐Olarte; François Rigal; Marco Girardello; Pedro Cardoso; Luís Carlos Crespo; Isabel R. Amorim; Miquel Arnedo; Mário Boieiro; José Carlos Carvalho; Rui Carvalho; Rosalina Gabriel; Lucas Lamelas‐Lopez; et al. (Journal of Biogeography, 2021)
Aim Habitat diversity has been linked to the diversity and structure of island communities, however, little is known about patterns and processes within habitats. Here we aim to determine the contributions of habitat type and inferred dispersal frequency to the differences in taxonomic structure between assemblages in the same island habitat. Location The Macaronesian archipelagos (Azores, Madeira, the Canary Islands and Cabo Verde). Taxon Spiders (Araneae). Methods We established forest and dry habitat sites (each with five plots) on two islands per archipelago. We collected spiders using standardised sampling protocols. We tested the differences in beta diversity separately for each habitat and for each inferred category of ballooning (an aerial dispersal strategy) frequency across geographic scales through nested non‐parametric permutational multivariate analyses of variance. We then tested whether ballooning and habitat influenced heterogeneity in species composition (dispersion in beta diversity) in the two habitat types. We analysed the effects of habitat and ballooning on species abundance distribution (SAD) and rarity by fitting Gambin models and evaluating the contribution of ballooning categories to SAD. Results Communities of the same archipelago and habitat were taxonomically more similar, and beta diversity increased with geographic scale, being greater in dry habitats. There was greater species replacement among assemblages in dry habitats than in forests, with greater differences for rare ballooners. There were no differences in SAD between habitats although dry habitat sites seemed to harbour more species with low abundances (rare species) than forests. Main conclusions Habitat type does not only condition the differences between spider assemblages of the same habitat but also the scale at which they occur. These differences may be determined by the heterogeneity in the physical structure of each habitat as well as how much this structure facilitates aerial dispersal (ballooning), and should be considered in theories/hypotheses on island community assembly as well as in conservation strategies.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Three new species of spiny mice, genus Neacomys Thomas, 1900 (Rodentia: Cricetidae), from Brazilian Amazonia - Thiago Borges Fernandes Semedo; Maria Nazareth Ferreira Da Silva; Ana Paula Carmignotto; Rogério Vieira Rossi (Systematics and Biodiversity, 2021)

Land cover along hiking trails in a nature tourism destination: the Azores as a case study - Diogo C. Pavão; João Porteiro; Maria A. Ventura; Lurdes Borges Silva; António Medeiros; Ana Moniz; Mónica Moura; Francisco Moreira; Luís Silva (Environment, Development and Sustainability, 2021)

A review exploring the overarching burden of Zika virus with emphasis on epidemiological case studies from Brazil - Merve Tunali; Alexandro André Radin; Selma Başıbüyük; Anwar Musah; Iuri Valerio Graciano Borges; Orhan Yenigun; Aisha Aldosery; Patty Kostkova; Wellington P. dos Santos; Tiago Massoni; Livia Marcia Mosso Dutra; Giselle Machado Magalhaes Moreno; et al. (Environmental Science and Pollution Research, 2021)
This paper explores the main factors for mosquito-borne transmission of the Zika virus by focusing on environmental, anthropogenic, and social risks. A literature review was conducted bringing together related information from this genre of research from peer-reviewed publications. It was observed that environmental conditions, especially precipitation, humidity, and temperature, played a role in the transmission. Furthermore, anthropogenic factors including sanitation, urbanization, and environmental pollution promote the transmission by affecting the mosquito density. In addition, socioeconomic factors such as poverty as well as social inequality and low-quality housing have also an impact since these are social factors that limit access to certain facilities or infrastructure which, in turn, promote transmission when absent (e.g., piped water and screened windows). Finally, the paper presents short-, mid-, and long-term preventative solutions together with future perspectives. This is the first review exploring the effects of anthropogenic aspects on Zika transmission with a special emphasis in Brazil.

Effects of intrinsic and extrinsic factors on the prevalence of the fungus Batrachochytrium dendrobatidis (Chytridiomycota) in stream tadpoles in the Atlantic Forest domain - Dener das Neves-da-Silva; Vitor Nelson Texeira Borges-Júnior; Christina Wyss Castelo Branco; Ana Maria Paulino Telles de Carvalho-e-Silva (Aquatic Ecology, 2021)

Dispersal syndromes are poorly associated with climatic niche differences in the Azorean seed plants - María Leo; Manuel J. Steinbauer; Paulo A.V. Borges; Eduardo B. de Azevedo; Rosalina Gabriel; Hanno Schaefer; Ana M.C. Santos (Journal of Biogeography, 2021)
Aim Environmental niche tracking is linked to the species ability to disperse. While well investigated on large spatial scales, dispersal constraints also influence small‐scale processes and may explain the difference between the potential and the realized niche of species at small scales. Here we test whether niche size and niche fill differ systematically according to dispersal syndrome within isolated oceanic islands. We expect that species with higher dispersal abilities (anemochorous or endozoochorous) will have a higher niche fill, despite their environmental niche size. Location Azores archipelago. Taxon Native seed plants. Methods We combined a georeferenced database of the species distribution within the archipelago (Azorean Biodiversity Portal/GBIF) with an expert‐based dispersal syndrome categorization and a high‐resolution climatic grid (CIELO model). Using four climatic variables (Annual Mean Temperature, Mean Diurnal Range, Annual Precipitation, Precipitation Seasonality), we calculated a four‐dimensional hypervolume to estimate the niche size of each species. Niche fill was quantified as the suitable climatic space of the island that was occupied by the focal species. Results We found a significant relationship between dispersal syndromes and niche size, and also between dispersal syndromes and niche fill. Such relationships presented no phylogenetic signal. Endozoochorous species display higher niche fill compared to epizoochorous and hydrochorous species, and larger niches than anemochorous and epizoochorous. Differences among the remaining groups are not significant for either niche size or for niche fill. Main conclusions The ability of a species to track its niche at small scales is not tightly related to its dispersal syndrome, although endozoochorous species track their niche more efficiently than the rest of groups. Despite being intuitively appealing, dispersal syndrome classifications might not be the most appropriate tools for understanding dispersal processes at small scales.

Seasonal dynamics of Amblyomma sculptum in two areas of the Cerrado biome midwestern Brazil, where human cases of rickettsiosis have been reported - Luiza Gabriella Ferreira de Paula; Viviane Zeringóta; Aparecida Lorrany Nunes Sampaio; Giovana Pereira Bezerra; Ana Laura Gonçalves Barreto; Andreza Alves dos Santos; Vanessa Carvalho Miranda; Warley Vieira de Freitas Paula; Lucianne Cardoso Neves; Mirna Vieira Secchis; Susy das Graças Alecrim Alves; Anaiá da Paixão Sevá; et al. (Experimental and Applied Acarology, 2021)

Impact of Diamondback Moth Density and Infestation Timing on Broccoli Yield - Elizeu de Sá Farias; Letícia Caroline da Silva Sant’ana; Júlia Borges Melo; Paulo Antonio Santana; Marcelo Coutinho Picanço (Neotropical Entomology, 2021)

Field Responses of Rice Stalk Stink Bug, Tibraca limbativentris, to Synthetic Sex Pheromone and Isomers of 1,10-Bisaboladien-3-ol - Thais F S De Freitas; E R Hickel; Ashot Khrimian; Miguel Borges; Mirian F F Michereff; José Alexandre Barrigossi; Raúl Alberto Laumann; S D Guggilapu; Josué Sant’Ana; Maria Carolina Blassioli-Moraes (Neotropical Entomology, 2021)

Integrating morphology and DNA barcoding to assess cetacean diversity in Brazil - Vanessa S. Silva; Natália Skueresky; Fernando Lopes; Tabata K. Koch; Paulo Henrique Ott; Salvatore Siciliano; André S. Barreto; Eduardo R. Secchi; Ana Carolina O. de Meirelles; Vitor Luz Carvalho; João C. G. Borges; Daniel Danilewicz; et al. (Mammal Research, 2021)

Serosurvey of West Nile virus (WNV) in free-ranging raptors from Brazil - Ana Paula Morel; Anelise Webster; Larissa Calo Zitelli; Karen Umeno; Ugo Araújo Souza; Fabiane Prusch; Marina Anicet; Gleide Marsicano; Paulo Bandarra; Gustavo Trainini; Julian Stocker; Denise Giani; et al. (Brazilian Journal of Microbiology, 2021)

Prospecting for Phytotoxicity and Enzymatic Modulation of Waters from Springs in the Surroundings of Campo Mourão, State of Paraná, Brazil, in Lactuca sativa L. - Sabrina Altmeyer Mendes; Letícia Scala Frâncica; Éderson Vecchietti Gonçalves; Leonardo Borges Coleto; João Victor Nunes Nicola; Ana Caroline Zago Pestana; Débora Cristina de Souza; Paulo Agenor Alves Bueno; Flávia Vieira da Silva Medeiros; Rafael Porto Ineu; Wyrllen Everson de Souza; Ana Paula Peron (Water, Air, & Soil Pollution, 2021)

Effect of Amoxicillin on Nitrogen Oxidation Bacteria Present in Activated Sludge: Respirometry Investigation - Júlia Kersul Faria; Ana Carolina Santana Conceição; Márcio Yukihiro Kohatsu; Alessandra Borges Okamoto; Lúcia Helena Coelho; Eduardo Lucas Subtil; Rodrigo de Freitas Bueno (Current Microbiology, 2021)

The decline of mussel aquaculture in the European Union: causes, economic impacts and opportunities - Lamprakis Avdelas; Edo Avdic‐Mravlje; Ana Cristina Borges Marques; Suzana Cano; Jacob J. Capelle; Natacha Carvalho; Maria Cozzolino; John Dennis; Tim Ellis; José M. Fernández Polanco; Jordi Guillen; Tobias Lasner; et al. (Reviews in Aquaculture, 2021)
In contrast to the increasing aquaculture production of mussels worldwide, production in the European Union (EU) has shown a decreasing trend over the last two decades. Aquaculture production of mussels in the EU peaked in the late 1990s at more than 600 000 tonnes; by 2016, production volume had dropped by 20% to 480 000 tonnes. As mussel production represents more than ⅓ of EU aquaculture production, this decrease is an important contributor to the stagnation of EU aquaculture. Previous studies have suggested diseases, lack of mussel seed (spat), and low profitability as the main causes of the EU mussel production decrease. In this study, we investigate how economic and environmental factors have contributed. Moreover, we examine if the different mussel production techniques (raft, longline, on‐bottom, and ‘bouchot’) have been differently affected, by analysing the economic performance and cost structure evolution for the period 2010–2016. We complement these results with a SWOT (strengths, weaknesses, opportunities, and threats) analysis of the EU mussel sector based on expert knowledge.

Caffeine has a dual influence on NMDA receptor–mediated glutamatergic transmission at the hippocampus - Robertta S. Martins; Diogo M. Rombo; Joana Gonçalves-Ribeiro; Carlos Meneses; Vladimir P. P. Borges-Martins; Joaquim A. Ribeiro; Sandra H. Vaz; Regina C. C. Kubrusly; Ana M. Sebastião (Purinergic Signalling, 2020)

PLA-PEG nanospheres decorated with phage display selected peptides as biomarkers for detection of human colorectal adenocarcinoma - Aline de Souza; William Castro-Borges; Milton Hércules Guerra de Andrade; Yara Cristina de Paiva Maia; Luiz Ricardo Goulart; Elisa Gomes Lanna; Ana Carolina Ferreira de Brito; Ana Paula Moreira Barboza; Vanessa Carla Furtado Mosqueira; Karina Taciana Santos Rubio (Drug Delivery and Translational Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Development and characterization of microsatellite markers in Stryphnodendron adstringens (Leguminosae) - Ariany Rosa Gonçalves; Luciana Oliveira Barateli; Ueric José Borges de Souza; Ana Maria Soares Pereira; Bianca Waléria Bertoni; Mariana Pires de Campos Telles (Physiology and Molecular Biology of Plants, 2020)

Drought-induced stress in leaves of Coix lacryma-jobi L. under exogenous application of proline and GABA amino acids - Rafael Agostinho Ferreira; Junior Borella; Cristina Moll Hüther; Ana Carolina Barbosa do Canto; Nathan Pereira da Costa Correa; Daniela Marques Correia; Rubiana Pereira Borges; Camila Ferreira de Pinho; Thelma de Barros Machado; Carlos Rodrigues Pereira (Brazilian Journal of Botany, 2020)

Oceanographic Determinants of the Abundance of Common Dolphins (Delphinus delphis) in the South of Portugal - Joana Castro; Ana Couto; Francisco O. Borges; André Cid; Marina I. Laborde; Heidi C. Pearson; Rui Rosa (Oceans, 2020)
Off mainland Portugal, the common dolphin (Delphinus delphis) is the most sighted cetacean, although information on this species is limited. The Atlantic coast of Southern Portugal is characterized by an intense wind-driven upwelling, creating ideal conditions for common dolphins. Using data collected aboard whale-watching boats (1929 sightings and 4548 h effort during 2010–2014), this study aims to understand the relationships between abundance rates (AR) of dolphins of different age classes (adults, juveniles, calves and newborns) and oceanographic [chlorophyll a (Chl-a) and sea surface temperature (SST)] variables. Over 70% of the groups contained immature animals. The AR of adults was negatively related with Chl-a, but not related to SST values. The AR of juveniles was positively related with SST. For calves and newborns, although the relationship between SST and AR is similar to that observed for juveniles, the effect could not be distinguished from zero. There was no relationship between Chl-a levels and the AR of juveniles, calves and newborns. These results corroborate previous findings that common dolphins tend to occur in highly productive areas demonstrating linkages between their abundance and oceanographic variables, and that this region may be a potential nursery ground.

Quality of Natural Waters Surrounding Campo Mourão, State of Paraná, Southern Brazil: Water Resources Under the Influences from Urban and Agricultural Activities - Sabrina Altmeyer Mendes; Éderson Vecchietti Gonçalves; Letícia Scala Frâncica; Leonardo Borges Coleto Correia; João Victor Nunes Nicola; Ana Caroline Zago Pestana; Flávia Vieira da Silva Medeiros; Wyrllen Everson de Souza; Rafael Porto Ineu; Ana Paula Peron (Water, Air, & Soil Pollution, 2020)

Genetic Structure Analysis in Sugarcane (Saccharum spp.) Using Target Region Amplification Polymorphism (TRAP) Markers Based on Sugar- and Lignin-Related Genes and Potential Application in Core Collection Development - Carlos Augusto Dias Kanthack Junior; João Ricardo Vieira Manechini; Ronan Xavier Corrêa; Ana Christina Rossini Pinto; Juliana Borges da Costa; Thais Monteiro Favero; Luciana Rossini Pinto (Sugar Tech, 2020)

Heavy metal concentrations in Brazilian port areas and their relationships with microorganisms: can pollution in these areas change the microbial community? - Bruna Del Busso Zampieri; Vanessa da Costa Andrade; Roberta Merguizo Chinellato; Carlos Alexandre Borges Garcia; Marcos Antônio de Oliveira; Gunther Brucha; Ana Julia Fernandes Cardoso de Oliveira (Environmental Monitoring and Assessment, 2020)

Endophytic bacteria naturally inhabiting commercial maize seeds occupy different niches and are efficient plant growth-promoting agents - Cláudia Silva Gomes Bomfim; Valéria Borges da Silva; Luiz Henrique Santos Cursino; Wesley da Silva Mattos; Jéssica Caroline Souza Santos; Layane Silva Barbosa de Souza; Bárbara França Dantas; Ana Dolores Santiago de Freitas; Paulo Ivan Fernandes-Júnior (Symbiosis, 2020)

Photocatalytic Properties of Commercially Available TiO2: Study of Fotosan® and InterBrasil® FA-101 for H2S Degradation Using UV and Solar Radiation - Eduardo Borges Lied; Camilo Freddy Mendoza Morejon; Rodrigo Leonardo de Oliveira Basso; Ana Paula Trevisan; Fernanda de Oliveira Tavares; Marcela Boroski; Jacqueline Ferandin Honório (Water, Air, & Soil Pollution, 2020)

Skull ontogenetic variation of the coastal developmental stage of the loggerhead turtle (Caretta caretta) in the western South Atlantic Ocean - Eduardo Araujo Lunardon; Luiz Ernesto Costa-Schmidt; Ana Júlia Lenz; Márcio Borges-Martins; Larissa Rosa de Oliveira (Hydrobiologia, 2020)

Essential oil and fractions isolated of Laurel to control adults and larvae of cattle ticks - Carla Maria Mariano Fernandez; Maurício Ferreira da Rosa; Ana Claudia Aparecida Mariano Fernandez; Wanessa de Campos Bortolucci; Fabiana Borges Padilha Ferreira; Giani Andrea Linde; Nelson Barros Colauto; Márcia Regina Simões; Viviane da Silva Lobo; Zilda Cristiani Gazim (Natural Product Research, 2020)

Hidden in the DNA: How multiple historical processes and natural history traits shaped patterns of cryptic diversity in an Amazon leaf‐litter lizard Loxopholis osvaldoi (Squamata: Gymnophthalmidae) - Sergio Marques-Souza; Katia C. Machado Pellegrino; Tuliana Oliveira Brunes; Ana Carolina Carnaval; Roberta Pacheco Damasceno; Manoela Lima de Oliveira Borges; Carlos Candia Gallardo; Miguel Trefaut Rodrigues (Journal of Biogeography, 2020)
Aim To investigate the cryptic diversity and diversification timing in the putatively low‐dispersal Amazonian leaf‐litter lizard Loxopholis osvaldoi , and to ask how geography (rivers, isolation by distance, IBD), ecological drivers (isolation by environment, IBE) and historical factors (climatic refugia) explain intraspecific genetic variation. Location Central Amazonia, Brazil. Taxon Squamata; Gymnophthalmidae; Loxopholis osvaldoi. Methods We sequenced two mitochondrial and two nuclear markers in 157 individuals. Phylogeographic structure and the occurrence of independent evolving lineages where explored through phylogenetic and coalescent analyses. A species tree and divergence dates of lineages were inferred with *BEAST, employing multiple DNA substitution rates. The potential genetic impacts of geographical distance among localities, the environment and the position of localities in relation to main rivers were tested by redundancy analysis (RDA). Results We detected 11 independently evolving and largely divergent intraspecific lineages. Lineage distribution patterns are complex and do not match any conspicuous barrier to gene flow, except for the Amazon River. Most lineages appear to have originated in the lower Miocene and Pliocene, in disagreement with the Pleistocene refuge hypothesis. IBD, IBE and rivers appear to have acted in concert establishing and maintaining genetic structure. However, when controlling for other explanatory variables, IBD explains significantly more variation than rivers, IBE or historical factors. Main Conclusions Our results strongly suggest that L . osvaldoi is a species complex. Future taxonomic work should use an integrative approach to explore whether morphological variation is present and congruent with the genetic data. While the use of a sensitive dating analysis allowed us to better describe the diversification history of L . osvaldoi , the lack of a spatial model of Neogene river dynamics prevents the test of specific, more informative river barrier hypotheses. The data suggest that nonlinear correlation analyses (e.g. RDA) should be preferred to detect factors that affect phylogeographic patterns in the Amazon, instead of linear multiple regressions (e.g. Mantel tests). Given the high level of cryptic diversity detected within this and other Amazonian species, we caution against hypothesis tests based solely on the distribution of nominal taxa, which can provide a rather incomplete view of the processes behind Amazonian diversity.

Male-Produced Sex Pheromone of Tibraca limbativentris Revisited: Absolute Configurations of Zingiberenol Stereoisomers and their Influence on Chemotaxis Behavior of Conspecific Females - M. C. Blassioli-Moraes; A. Khrimian; M. F. F. Michereff; D. M. Magalhães; E. Hickel; T. F. S. de Freitas; J. A. F. Barrigossi; R. A. Laumann; A. T. Silva; S. D. Guggilapu; C. C. Silva; J. Sant’Ana; et al. (Journal of Chemical Ecology, 2020)

In vitro antibacterial and time-kill assay of ethanolic extract of Davilla nitida bark on multidrug resistant bacteria isolated from diabetic foot lesions - Michele Cezimbra Perim; Joelma da Costa Borges; Eulália Maria Lima da Silva; Thiago Antônio de Sousa Araújo; Ana Carolina Oliveira da Silva; Valéria Christiane da Silva; Solange Cristina Carreiro; Anderson Ferreira Cunha; Maria Cristina da Silva Pranchevicius (Natural Product Research, 2019)

First indication of deleterious impacts in white-seabream larvae (Diplodus sargus) survival and behaviour following acute venlafaxine exposure - Ana Rodrigues; Francisco O. Borges; Vasco Pissarra; Ana Luísa Maulvault; José R. Paula; Regina Bispo; Rui Rosa (Ecotoxicology, 2019)

Sensitivity and specificity of the FAMACHA© system in tropical hair sheep - Josiel Borges Ferreira; Cristina Santos Sotomaior; Ana Carla Diógenes Suassuna Bezerra; Wilma Emanuela da Silva; Jacinara Hody Gurgel Morais Leite; José Ernandes Rufino de Sousa; Jesséa de Fátima França Biz; Débora Andréa Evangelista Façanha (Tropical Animal Health and Production, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Crown gall caused by Agrobacterium tumefaciens species complex: a novel nursery disease of Tectona grandis in Brazil - Rafaela C. F. Borges; Maurício Rossato; Greecy Mirian R. Albuquerque; Maria A. Ferreira; Ana C. M. Brasileiro; Maria Esther N. Fonseca; Leonardo Silva Boiteux (Journal of Plant Pathology, 2019)

Optimization of Chitosan-α-casein Nanoparticles for Improved Gene Delivery: Characterization, Stability, and Transfection Efficiency - João Panão Costa; Sofia Carvalho; Sandra Jesus; Edna Soares; Ana Patrícia Marques; Olga Borges (AAPS PharmSciTech, 2019)

Combined transcriptomics–metabolomics profiling of the heat shock response in the hyperthermophilic archaeon Pyrococcus furiosus - Ana M. Esteves; Gonçalo Graça; Lindsay Peyriga; Inês M. Torcato; Nuno Borges; Jean-Charles Portais; Helena Santos (Extremophiles, 2019)

Study of tensiometric properties, microbiological and collagen content in nile tilapia skin submitted to different sterilization methods - Ana Paula Negreiros Nunes Alves; Edmar Maciel Lima Júnior; Nelson Sarto Piccolo; Marcelo José Borges de Miranda; Maria Elisa Quezado Lima Verde; Antônio Ernando Carlos Ferreira Júnior; Paulo Goberlânio de Barros Silva; Victor Pinheiro Feitosa; Tereza Jesus Pinheiro Gomes de Bandeira; Monica Beatriz Mathor; Manoel Odorico de Moraes (Cell and Tissue Banking, 2018)

The occurrence of wild cotton Gossypium mustelinum Miers ex Watt populations in the coast of Pernambuco, Northeastern Brazil - Edson Ferreira da Silva; Luiz Sergio Costa Duarte Filho; Ana Kelly dos Santos Maia; Allison Vieira da Silva; Ana Carolina Borges Lins e Silva (Genetic Resources and Crop Evolution, 2018)

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Human bocavirus in hospitalized children under 5 years with acute respiratory infection, São Paulo, Brazil, 2010 - Patricia Evelin Silva; Cristina Adelaide Figueiredo; Adriana Luchs; Terezinha Maria de Paiva; Margarete Aparecida Benega Pinho; Renato Sousa Paulino; Daniela Bernardes Borges da Silva; Katia Corrêa de Oliveira Santos; Ana Maria Sardinha Afonso; Maria Isabel de Oliveira (Archives of Virology, 2018)

PROJECT AQUA&AMBI Support to wetland management in the southwest Iberia coastal zone: interactions between Aquaculture and Environment in the Euroregion Alentejo-Algarve-Andalusia - Carlos Sousa; Laura Ribeiro; Ana Magalhães; Patricia Simões; Cristina Borges; Laura Mestre; Jose Viegas; Maria Cunha (Frontiers in Marine Science, 2018)

Evaluation of antibacterial activity of the bark and leaf extracts of Brosimum gaudichaudii Trécul against multidrug resistant strains - Joelma da Costa Borges; Michele Cezimbra Perim; Rodrigo Orlandini de Castro; Thiago Antônio de Sousa Araújo; Tadeu José da Silva Peixoto Sobrinho; Ana Carolina Oliveira da Silva; Sandra Maria Botelho Mariano; Solange Cristina Carreiro; Maria Cristina da Silva Pranchevicius (Natural Product Research, 2017)

Production of Electrospun Fast-Dissolving Drug Delivery Systems with Therapeutic Eutectic Systems Encapsulated in Gelatin - Francisca Mano; Marta Martins; Isabel Sá-Nogueira; Susana Barreiros; João Paulo Borges; Rui L. Reis; Ana Rita C. Duarte; Alexandre Paiva (AAPS PharmSciTech, 2017)

rs3851179 Polymorphism at 5′ to the PICALM Gene is Associated with Alzheimer and Parkinson Diseases in Brazilian Population - Cíntia Barros Santos-Rebouças; Andressa Pereira Gonçalves; Jussara Mendonça dos Santos; Bianca Barbosa Abdala; Luciana Branco Motta; Jerson Laks; Margarete Borges de Borges; Ana Lúcia Zuma de Rosso; João Santos Pereira; Denise Hack Nicaretta; Márcia Mattos Gonçalves Pimentel (NeuroMolecular Medicine, 2017)

Traits and functional strategies as predictors of demographic variations over a chronosequence - Maria Amanda Menezes Silva; Andréa de Vasconcelos Freitas Pinto; Ladivania Medeiros do Nascimento; Ana Carolina Borges Lins-e-Silva; André Luiz Alves de Lima; Everardo Valadares de Sá Barretto Sampaio; Maria Jesus Nogueira Rodal (Brazilian Journal of Botany, 2017)

Quinoa: Nutritional, functional, and antinutritional aspects - Antonio Manoel Maradini Filho; Mônica Ribeiro Pirozi; João Tomaz Da Silva Borges; Helena Maria Pinheiro Sant'Ana; José Benício Paes Chaves; Jane Sélia Dos Reis Coimbra (Critical Reviews in Food Science and Nutrition, 2017)

A roadmap for island biology: 50 fundamental questions after 50 years of The Theory of Island Biogeography - Jairo Patiño; Robert J. Whittaker; Paulo A.V. Borges; José María Fernández‐Palacios; Claudine Ah‐Peng; Miguel B. Araújo; Sergio P. Ávila; Pedro Cardoso; Josselin Cornuault; Erik J. de Boer; Lea de Nascimento; Artur Gil; et al. (Journal of Biogeography, 2017)
Aims The 50th anniversary of the publication of the seminal book, The Theory of Island Biogeography , by Robert H. MacArthur and Edward O. Wilson, is a timely moment to review and identify key research foci that could advance island biology. Here, we take a collaborative horizon‐scanning approach to identify 50 fundamental questions for the continued development of the field. Location Worldwide. Methods We adapted a well‐established methodology of horizon scanning to identify priority research questions in island biology, and initiated it during the Island Biology 2016 conference held in the Azores. A multidisciplinary working group prepared an initial pool of 187 questions. A series of online surveys was then used to refine a list of the 50 top priority questions. The final shortlist was restricted to questions with a broad conceptual scope, and which should be answerable through achievable research approaches. Results Questions were structured around four broad and partially overlapping island topics, including: (Macro)Ecology and Biogeography, (Macro)Evolution, Community Ecology, and Conservation and Management. These topics were then subdivided according to the following subject areas: global diversity patterns (five questions in total); island ontogeny and past climate change (4); island rules and syndromes (3); island biogeography theory (4); immigration–speciation–extinction dynamics (5); speciation and diversification (4); dispersal and colonization (3); community assembly (6); biotic interactions (2); global change (5); conservation and management policies (5); and invasive alien species (4). Main conclusions Collectively, this cross‐disciplinary set of topics covering the 50 fundamental questions has the potential to stimulate and guide future research in island biology. By covering fields ranging from biogeography, community ecology and evolution to global change, this horizon scan may help to foster the formation of interdisciplinary research networks, enhancing joint efforts to better understand the past, present and future of island biotas.

The role of plant fidelity and land-use changes on island exotic and indigenous canopy spiders at local and regional scales - Margarita Florencio; François Rigal; Paulo A. V. Borges; Pedro Cardoso; Ana M. C. Santos; Jorge M. Lobo (Biological Invasions, 2016)

Development of an autonomous system for integrated marine monitoring - Magalhães Catarina; Mucha Ana Paula; Carvalho Maria; Ribeiro Hugo; Almeida Cristina; Azevedo Isabel; Ramos Sandra; Borges Teresa; Leandro Sérgio; Dos Santos Antonina; Silva Alexandra; Bartilotti Cátia; et al. (Frontiers in Marine Science, 2016)

Science, technology and society initiative to minimise unwanted catches in European fisheries – the MINOUW Project (EU H2020 RIA) - Rangel Mafalda; Anjos Mariana; Bentes Luis; Borges Teresa; Campos Aida; Castro Margarida; Eichert Morritz; Fonseca Paulo; Gaspar Miguel; Gonçalves Jorge; Guimarães Helena; Marçalo Ana; et al. (Frontiers in Marine Science, 2016)

Potential of two populations of Amblyseius swirskii (Acari: Phytoseiidae) for the control of Bemisia tabaci biotype B (Hemiptera: Aleyrodidae) in Brazil - Ana Cristina Cerqueira Cavalcante; Lucas Rosa Borges; André Luiz Lourenção; Gilberto José de Moraes (Experimental and Applied Acarology, 2015)

Hercinothrips dimidiatus Hood (Thysanoptera: Thripidae), a new pest of Aloe arborescens Miller in Europe - Célia Mateus; José Carlos Franco; Maria Filomena Caetano; Elsa Borges da Silva; Ana Paula Ramos; Elisabete Figueiredo; Laurence Mound (Phytoparasitica, 2015)

Does the plant economics spectrum change with secondary succession in the forest? - Maria Amanda Menezes Silva; Andréa de Vasconcelos Freitas Pinto; Ladivania Medeiros do Nascimento; Ana Carolina Borges Lins-e-Silva; André Luiz Alves de Lima; Maria Jesus Nogueira Rodal (Trees, 2015)

Effects of palatable cafeteria diet on cognitive and noncognitive behaviors and brain neurotrophins’ levels in mice - Daniela D. Leffa; Samira S. Valvassori; Roger B. Varela; Jésica Lopes-Borges; Francine Daumann; Luiza M. Longaretti; Ana Luiza F. Dajori; João Quevedo; Vanessa M. Andrade (Metabolic Brain Disease, 2015)

Experimental infection of inbred BALB/c and A/J mice with Massachusetts and Brazilian strains of infectious bronchitis virus (IBV) - Matheus C. Martini; Jacy Gameiro; Tereza Cristina Cardoso; Leonardo C. Caserta; Ana Carolina M. Gualberto; Lara Borges Keid; Trícia M. F. de S. Oliveira; Marcia M. A. B. dos Santos; Clarice W. Arns; Helena L. Ferreira (Archives of Virology, 2015)

Risk factors to incidental leptospirosis and its role on the reproduction of ewes and goats of Espírito Santo state, Brazil - Priscilla Cortizo; Ana Paula Loureiro; Gabriel Martins; Patrícia Rosário do Rodrigues; Braulio Pego Faria; Walter Lilenbaum; Bruno Borges Deminicis (Tropical Animal Health and Production, 2015)

Patterns of recruitment of the sand smelt (Atherina presbyter) on rocky intertidal habitats - Lungu Ruxanda; Coelho Pedro; Neto José; Rodrigues Diana; Faria Ana; Borges Rita; Gonçalves Emanuel; Almada Frederico (Frontiers in Marine Science, 2015)

Transformation of Tributyltin in Zebrafish Eleutheroembryos (Danio rerio) - Aline Rocha Borges; Ana López-Serrano Oliver; Mercedes Gallego-Gallegos; Riansares Muñoz-Olivas; Maria Goreti Rodrigues Vale; Carmen Cámara (Biological Trace Element Research, 2014)

Recombinant dengue 2 virus NS3 protein conserves structural antigenic and immunological properties relevant for dengue vaccine design - Rosa Ramírez; Rosabel Falcón; Alienys Izquierdo; Angélica García; Mayling Alvarez; Ana Beatriz Pérez; Yudira Soto; Mayra Muné; Emiliana Mandarano da Silva; Oney Ortega; Ronaldo Mohana-Borges; María G. Guzmán (Virus Genes, 2014)

In vitro organogenesis from root culture segments of Bixa orellana L. (Bixaceae) - Ana Claudia Ferreira da Cruz; Diego Ismael Rocha; Lourdes Iarema; Marília Contim Ventrella; Marcio Gilberto Cardoso Costa; Vespasiano Borges Paiva Neto; Wagner Campos Otoni (In Vitro Cellular & Developmental Biology - Plant, 2014)

Evaluation of the effects of selected phytochemicals on quorum sensing inhibition and in vitro cytotoxicity - Anabela Borges; Sofia Serra; Ana Cristina Abreu; Maria J. Saavedra; António Salgado; Manuel Simões (Biofouling, 2014)

Assessment of solar driven TiO2-assisted photocatalysis efficiency on amoxicillin degradation - João H. O. S. Pereira; Ana C. Reis; Olga C. Nunes; Maria T. Borges; Vítor J. P. Vilar; Rui A. R. Boaventura (Environmental Science and Pollution Research, 2014)

Changes in natural killer cell subpopulations over a winter training season in elite swimmers - Luís Rama; Ana Maria Teixeira; Alice Matos; Grasiely Borges; Ana Henriques; Michael Gleeson; Susana Pedreiro; Edith Filaire; Francisco Alves; Artur Paiva (European Journal of Applied Physiology, 2013)

How do different dispersal modes shape the species–area relationship? Evidence for between‐group coherence in the M acaronesian flora - Silvia C. Aranda; Rosalina Gabriel; Paulo A. V. Borges; Ana M. C. Santos; Joaquín Hortal; Andrés Baselga; Jorge M. Lobo (Global Ecology and Biogeography, 2013)
Aim We explore the island species–area relationships ( ISARs ) of several plant groups differing in dispersal ability. We examine whether: (i) the ISAR slope is higher for less dispersive groups (diminishing from not‐wind‐dispersed seed plants to wind‐dispersed seed plants, pteridophytes and bryophytes); and (ii) the regional richness is higher than that predicted by the ISAR of its constituent islands for groups with lower dispersal ability. Additionally, we relate both patterns to the compositional dissimilarity (beta diversity) between islands. Location The M acaronesian archipelagos of the A zores, M adeira and C anary I slands. Methods ISARs were estimated using the conventional power model. Differences in slopes among taxa were analysed through ANCOVA tests. We assessed the deviation of the total richness of the M acaronesian flora from that predicted by the ISAR and calculated several measures of beta diversity (turnover, nestedness‐resultant dissimilarity and nestedness). Analyses were repeated after excluding the two C anarian islands of L anzarote and F uerteventura, which have unique climatic and geological conditions in the region. Results All ISAR models were significant except for pteridophytes (for which it was significant when excluding L anzarote and F uerteventura). ISAR slopes did not differ among taxa. Regional richness followed ISAR predictions for bryophytes and pteridophytes when L anzarote and F uerteventura were excluded, while the total number of M acaronesian seed plants (particularly not‐wind‐dispersed species) always fell above the ISAR . Turnover was higher in seed plants than in bryophytes and pteridophytes, and the opposite occurred with nestedness. Main conclusions Differences in dispersal ability influence the compositional dissimilarity between these islands, but not the rate of species increase with area. This may be because ISAR slopes are mostly determined by within‐island processes of species accumulation, while differences in dispersal generate different between‐island patterns. The lack of relationship between the ISAR slope and species replacement or nestedness prevents its use as a proxy for beta diversity.

P2X7 receptor activation leads to increased cell death in a radiosensitive human glioma cell line - Marina Petersen Gehring; Talita Carneiro Brandão Pereira; Rafael Fernandes Zanin; Magali Carvalho Borges; Aroldo Braga Filho; Ana Maria Oliveira Battastini; Maurício Reis Bogo; Guido Lenz; Maria Martha Campos; Fernanda Bueno Morrone (Purinergic Signalling, 2012)

Cardiac Rhythm Disturbances Associated with Amlodipine Acute Intoxication - Carlos Henrique Miranda; Leudo Xavier; Flávio Fiorante; Gustavo Prata Misiara; Ellen Gonçalves Guimarães; Ana Marta Galli; Antônio Pazin-Filho; Marcos de Carvalho Borges (Cardiovascular Toxicology, 2012)

Resolving the Azorean knot: a response to Carine & Schaefer (2010) - Kostas A. Triantis; Joaquín Hortal; Isabel Amorim; Pedro Cardoso; Ana M. C. Santos; Rosalina Gabriel; Paulo A. V. Borges (Journal of Biogeography, 2012)
Carine & Schaefer ( Journal of Biogeography , 2010, 37 , 77–89) suggest that the lack of past climate oscillations in the Azores may have contributed to the low plant endemism in this archipelago compared to that of the Canary Islands, a pattern they term the Azorean diversity enigma. Here we challenge their hypothesis, and discuss how the particular characteristics of the Azores may have driven current diversification patterns in this archipelago. We argue that the restricted number of Azorean endemic species and their wide distribution is explicable by the geological, geographical and ecological attributes of the archipelago. That is, the Azores are too young, too small, and too environmentally homogeneous to have hosted many in situ diversification events, so they do not host as many endemic species as other Macaronesian archipelagos, such as Madeira and especially the Canary Islands.

First record of the pepper tree psyllid, Calophya schini Tuthill (Hemiptera, Calophyidae), in the Palaearctic region - Vera Zina; Arlindo Lima; Filomena Caetano; Elsa Borges da Silva; Ana Paula Ramos; José Carlos Franco (Phytoparasitica, 2012)

Establishment of adventitious root culture of Stevia rebaudiana Bertoni in a roller bottle system - Rafael Valim Reis; Ana Paula Patrão Luis Borges; Talita Perez Cantuaria Chierrito; Eliezer Rodrigues de Souto; Lauro Mera de Souza; Marcello Iacomini; Arildo José Braz de Oliveira; Regina Aparecida Correia Gonçalves (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Phylogenetic Groups Among Klebsiella pneumoniae Isolates from Brazil: Relationship with Antimicrobial Resistance and Origin - Maíra Espíndola Silva de Melo; Adriane Borges Cabral; Maria Amélia Vieira Maciel; Vera Magalhães da Silveira; Ana Catarina de Souza Lopes (Current Microbiology, 2011)

Enzymatic Activity, Sensitivity to Antifungal Drugs and Baccharis dracunculifolia Essential Oil by Candida Strains Isolated from the Oral Cavities of Breastfeeding Infants and in Their Mothers’ Mouths and Nipples - Cristiane Aparecida Pereira; Anna Carolina Borges Pereira da Costa; Ana Karina Silva Machado; Miltom Beltrame Júnior; Maria Stella Amorin Costa Zöllner; Juliana Campos Junqueira; Antonio Olavo Cardoso Jorge (Mycopathologia, 2011)

The Azorean Biodiversity Portal: An internet database for regional biodiversity outreach - PAULO A.V. BORGES †; ROSALINA GABRIEL †; ANA M. ARROZ †; ANA COSTA †; REGINA T. CUNHA †; LUÍS SILVA †; ENÉSIMA MENDONÇA †; ANTÓNIO M. F. MARTINS †; FRANCISCO REIS †; PEDRO CARDOSO † (Systematics and Biodiversity, 2010)

Molecular characterization of adenovirus detected from fecal samples obtained from children in the Central West region of Brazil - Erika Regina L. de Freitas; Ana Maria T. Borges; Fabíola S. Fiaccadori; Menira B. L. D. e Souza; Divina das Dôres P. Cardoso (Archives of Virology, 2010)

Are species–area relationships from entire archipelagos congruent with those of their constituent islands? - Ana M. C. Santos; Robert J. Whittaker; Kostas A. Triantis; Paulo A. V. Borges; Owen R. Jones; Donald L. J. Quicke; Joaquín Hortal (Global Ecology and Biogeography, 2010)
Aim To establish the extent to which archipelagos follow the same species–area relationship as their constituent islands and to explore the factors that may explain departures from the relationship. Location Thirty‐eight archipelagos distributed worldwide. Methods We used ninety‐seven published datasets to create island species–area relationships (ISARs) using the Arrhenius logarithmic form of the power model. Observed and predicted species richness of an archipelago and of each of its islands were used to calculate two indices that determined whether the archipelago followed the ISAR. Archipelagic residuals ( ArcRes ) were calculated as the residual of the prediction provided by the ISAR using the total area of the archipelago, standardized by the total richness observed in the archipelago. We also tested whether any characteristic of the archipelago (geological origin and isolation) and/or taxon accounts for whether an archipelago fits into the ISAR or not. Finally, we explored the relationship between ArcRes and two metrics of nestedness. Results The archipelago was close to the ISAR of its constituent islands in most of the cases analysed. Exceptions arose for archipelagos where (i) the slopes of the ISAR are low, (ii) observed species richness is higher than expected by the ISAR and/or (iii) distance to the mainland is small. The archipelago's geological origin was also important; a higher percentage of oceanic archipelagos fit into their ISAR than continental ones. ArcRes indicated that the ISAR underpredicts archipelagic richness in the least isolated archipelagos. Different types of taxon showed no differences in ArcRes . Nestedness and ArcRes appear to be related, although the form of the relationship varies between metrics. Main conclusions Archipelagos, as a rule, follow the same ISAR as their constituent islands. Therefore, they can be used as distinct units themselves in large‐scale biogeographical and macroecological studies. Departure from the ISAR can be used as a crude indicator of richness‐ordered nestedness, responsive to factors such as isolation, environmental heterogeneity, number and age of islands.

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

Comparative study of the thermostabilizing properties of mannosylglycerate and other compatible solutes on model enzymes - Nuno Borges; Ana Ramos; Neil Raven; Richard Sharp; Helena Santos (Extremophiles, 2002)

The role of 2,6-dichlorophenol as sex pheromone of the tropical horse tick Anocentor nitens (Acari: Ixodidae) - Lígia M.F. Borges; Álvaro Eduardo Eiras; Pedro Henrique Ferri; Ana Cristina Côrtes Lôbo (Experimental and Applied Acarology, 2002)